Top layer system for absorbent articles

JP2025506742AInactive Publication Date: 2025-03-13PROCTER & GAMBLE CO
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024549244
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-03
Filing Date
2023-03-03
Publication Date
2025-03-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

的な吸収及び清潔さの認識のために)それを通して見ることから、実用的に最大限に隠す。 -着用者の皮膚に対して柔らかく快適であり、流体侵入後を含めて乾燥している感触である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506742000001_ABST
    Figure 2025506742000001_ABST
Patent Text Reader

Abstract

A feminine hygiene pad is disclosed having a monolithic fibrous nonwoven web topsheet, the web comprising bicomponent staple topsheet fibers having an average denier of 3.0-5.0 and a sheath-core bicomponent configuration, the sheath component comprising polyethylene (PE) and the core component comprising polyethylene terephthalate (PET) with a weight ratio of PE:PET of 40:60-60:40, the fibers comprising hydrophobic fibers, the web comprising interfiber bonds randomly distributed within the web along the x-, y-, and z-directions, the interfiber bonds being present where the sheaths of adjacent fibers are fusion bonded together without compression.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Absorbent articles of various designs have been used for many years to intercept, capture, contain, and absorb bodily exudates, including menstrual fluid, urine, and feces, and to manage the exudates to avoid soiling of undergarments, outerwear, bedding, and the like.

[0002] Feminine hygiene pads (also known as "sanitary napkins", "menstrual pads", etc.), one type of absorbent article, have been used by women to manage menstrual discharge during menstruation. A typical feminine hygiene pad includes a liquid permeable topsheet forming the body / wear-facing surface of the pad, a liquid impermeable backsheet forming the outward-facing surface of the pad and acting as a barrier to prevent fluids absorbed by the pad from migrating outward to the outward-facing surface of the pad, and an absorbent structure performing more or less any desired combination of fluid handling functions including blocking, distributing within the pad, absorbing, containing, and storing fluids during the desired wear / use period of the pad. A typical pad is constructed, shaped, and sized to be placed and worn inside the crotch region of the intended user's pants. Many pads include one or more deposits of adhesive on the outward-facing surface of the backsheet to allow the wearer to affix the pad to the inner surface of the undergarment to help hold it in place during wear / use.

[0003] A variety of materials have been developed and used to form topsheets for feminine hygiene pads.

[0004] In some examples, the topsheet may be formed of a polymeric film having a pattern of holes formed therein. The holes serve to allow exuded fluid to pass through the topsheet and transfer to the absorbent component of the pad disposed thereunder. However, some segments of the consumer market may not prefer film topsheets for a variety of reasons, which may include skin feel.

[0005] In another example, the topsheet may be formed from a fibrous nonwoven web material. A myriad of combinations of nonwoven characteristics are possible. The fibrous components may be relatively long fibers of indefinite and varying lengths, or may be staple fibers. They may include natural fibers (e.g., cotton fibers), semi-synthetic fibers such as regenerated cellulose (rayon) fibers. They may include monocomponent fibers or multicomponent fibers. The fibers may be relatively straight, curled, or crimped. Spun fibers may be spun from various polymeric components. The precursor batt or collection of constituent fibers may be consolidated, the fibers held together, such that the web has cloth-like properties and structural integrity imparted by various mechanisms, including fiber entanglement, interfiber fusion bonding, interfiber binder / adhesive bonding, and the like. Any desired selection of various types of fibers may be incorporated, layered, and / or mixed in any desired weight ratio to form the nonwoven web. Any portion or all of the constituent fibers or nonwoven web may be treated to impart or increase hydrophobicity or hydrophilicity, or any combination or arrangement thereof, to the fiber surfaces.

[0006] Generally, it is desired by users that the topsheet of a feminine hygiene pad be: - Easily accepts menstrual fluid and promotes its rapid passage downward in the z-direction through it to the underlying absorbent component (rapid acquisition). - Resists spreading of menstrual fluid in the xy direction and resists contamination by menstrual fluid. - Resists reacquisition of fluid from the underlying absorbent component and resists fluid migration in the z-direction upwards through it (rewetting) and back to the surface facing the wearer (thereby causing a wet feeling to the wearer and / or the perception of incomplete absorption and less effective protection). -Hides menstrual fluid absorbed by the underlying absorbent component from view therethrough to the greatest extent practical (for effective absorption and the perception of cleanliness). - Feels soft and comfortable against the wearer's skin and is dry to the touch, even after fluid ingress.

[0007] These objectives are somewhat conflicting. For example, a topsheet of a nonwoven web material that easily wicks fluid downward in the z-direction may also tend to retain some fluid, or easily wick fluid back upward in the z-direction (rewetting), or wick fluid along the xy-direction, causing soiling. Conversely, a topsheet that resists fluid movement in the z-direction from the absorbent component to the surface facing the wearer may also resist fluid movement / wicking in the xy-direction, but may not readily accept and pass fluid to the absorbent component (i.e., exhibit slow acquisition). A web with substantial permeability (e.g., provided by a large pore volume) may readily accept and pass fluid, but may be insufficiently mechanically robust to be processed on a conversion line, or may be insufficiently opaque or substantially insufficiently visual to be acceptable to the consumer / user. Various approaches have been attempted to meet the conflicting objectives as much as possible through the myriad combinations of different components, configurations, and features identified above. However, opportunities for improvement remain. [Brief description of the drawings]

[0008] While the specification concludes with claims particularly pointing out and distinctly claiming the subject matter regarded as the invention, it is believed that the invention will be more fully understood from the following description read in conjunction with the accompanying drawings, in which: Some of the figures may be simplified by omitting selected elements for the purpose of more clearly showing other elements. The omission of such elements in some of the figures does not necessarily indicate the presence or absence of a particular element in any of the illustrative embodiments, unless expressly depicted in the corresponding written description. None of the drawings are necessarily to scale. [Figure 1A] FIG. 2 is a schematic plan view (along the z-direction) of an example absorbent article. [Figure 1B] FIG. 1B is a schematic plan view (along the z-direction) of an example absorbent core component layer of the absorbent article shown in FIG. 1A. [Diagram 2] 1A-1C are schematic diagrams of example equipment layouts and processes that may be configured to manufacture a fluid management layer. [Diagram 3] FIG. 2 is a schematic diagram of an example cross-section of a fluid management layer along the z-plane. [Figure 4] 1 is a top view image (along the z-direction) of a portion of a nonwoven web material having a pattern of holes therethrough. [Diagram 5] 1 is a top view (along the z-direction) enlarged image of a portion of a nonwoven web material having holes therethrough. [Figure 6] FIG. 2 is a top view of a strikethrough plate used in the acquisition time and rewet measurements described herein. [Figure 7] FIG. 2 is a bottom view of a strikethrough plate used in the acquisition time and rewet measurements described herein. [Figure 8A] FIG. 7 is a cross-sectional view along the plane defined by the z-direction and line AA shown in FIG. 6 of a strikethrough plate used in the capture time and rewet measurements described herein. [Figure 8B] FIG. 7 is a cross-sectional view of a penetration plate used in the capture time and rewet measurements described herein, taken along the plane defined by the z direction and line BB shown in FIG. 6. [Figure 9] 1 is a chart showing the second acquisition times measured for eight prototype feminine hygiene pad samples, as measured using the acquisition time and rewet measurement methods described herein. [Figure 10] 1 is a chart showing the measured surface free fluid (SFF) and total rewet for 10 prototype feminine hygiene pad samples, as measured using the acquisition time and rewet measurement methods described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] definition As used herein, the following terms shall have the meanings specified below.

[0010] "Absorbent article" refers to a wearable device that absorbs and / or contains liquids, and more specifically, refers to a device that is placed against or in proximity to the body of a wearer to absorb and contain various bodily exudates. Absorbent articles can include feminine hygiene products including diapers, training pants, adult incontinence undergarments (e.g., liners, pads, and briefs), and / or feminine hygiene pads (e.g., also known as "sanitary napkins," "menstrual pads," "panty liners," etc.).

[0011] As used herein, the term "integrated" is used to describe fibers of a nonwoven material that are twisted, entangled, and / or pushed / pulled in the positive and / or negative Z direction (thickness direction of the nonwoven material). Some exemplary processes for consolidating fibers of a nonwoven web include spunlacing and needlepunching. Spunlacing (also known as "hydroentanglement" or "hydroenhancing") uses multiple high-pressure water jets directed at a precursor batt or collection of fibers transported along the machine direction to entangle the fibers. Needlepunching (also known as "needling") involves using specially equipped needles to mechanically push and / or pull the fibers of a precursor batt or collection of fibers in the z direction and entangle them with other fibers in the batt or collection.

[0012] As used herein, the term "carded" is used to describe the structural characteristics of the fluid management layer described herein. Carded nonwovens are formed of fibers cut to a specific finite length, also known as "staple filaments". The staple filaments can be of any selected length. For example, the staple filaments can be cut to lengths as short as 10 mm, down to a maximum length of 120 mm. However, when a particular group of fibers is staple filaments, the length of each of the fibers in the carded nonwoven is approximately the same, i.e., staple length. When fibers of two or more compositions are included in a nonwoven web, such as a web containing polypropylene fibers and viscose fibers, the length of each of the fibers of the same composition can be substantially the same, but the length of each of the staple fibers of each fiber composition can be different.

[0013] In contrast to staple fibers, filaments, such as those produced by spinning in spunbond or meltblown nonwoven web manufacturing processes, are typically not staple filaments. Instead, these filaments may be characterized as "continuous" fibers, meaning that they are of relatively long and indefinite length and are not cut to specific lengths after spinning, like their staple fiber counterparts.

[0014] "Lateral" refers to an absorbent article, such as a feminine hygiene pad, or a component thereof, in a direction parallel to a horizontal line tangent to the front of the upper part of the wearer's legs adjacent the torso when the pad is normally worn and the wearer is in an even, straight, normal standing position. The "width" dimension of any component or feature of an article, such as a feminine hygiene pad, is measured along the lateral direction. When the article or a component thereof is placed flat on a horizontal surface, the "lateral" direction corresponds to the lateral direction relative to the structure when it is worn, as defined above. With respect to an article, such as a feminine hygiene pad, that is opened and placed flat on a horizontal plane, "lateral" refers to a direction perpendicular to the longitudinal direction and parallel to the horizontal plane. With respect to a feminine hygiene pad, the term "y-direction" is interchangeable with the term "longitudinal direction".

[0015] The "lateral axis" of an absorbent article, such as a feminine hygiene pad or component thereof, is the horizontal line that lies in the xy plane and equally divides the length of the pad or component when the pad or component is laid flat on a horizontal surface. The transverse axis is perpendicular to the longitudinal axis.

[0016] "Longitudinal" refers to the direction perpendicular to the lateral direction with respect to an absorbent article, such as a feminine hygiene pad, or a component thereof. The "length" dimension of any component or feature of the article is measured along the longitudinal direction from its front extent to its rear extent. When an article, such as a feminine hygiene pad, or a component thereof, is placed flat on a horizontal surface, the "longitudinal" direction is perpendicular to the lateral direction with respect to the pad when worn, as defined above. With respect to feminine hygiene pads, the term "y-direction" is interchangeable with the term "longitudinal".

[0017] The "longitudinal axis" of a feminine hygiene pad or component thereof is the longitudinal line that lies in the xy plane and divides the width of the pad or component when the pad is laid flat on a horizontal surface. The longitudinal axis is perpendicular to the horizontal axis.

[0018] As used herein, the term "rayon" is used generically to include any fiber spun from regenerated cellulose, including but not limited to viscose, lyocell, and the like.

[0019] With respect to an absorbent article, such as a feminine hygiene pad, or a component thereof, when placed flat on a horizontal surface, the "xy-plane" means any horizontal plane occupied by the horizontal surface or any layer of the article or component. With respect to the manufacture or processing of a web of material, the term "xy-plane" refers to the plane substantially occupied by a major surface of the web of material.

[0020] With respect to the manufacturing or processing of a web of material, the term "x-direction" is interchangeable with the term "cross direction."

[0021] With respect to the manufacturing or processing of a web of material, the term "y-direction" is interchangeable with the term "machine direction."

[0022] In the context of an absorbent article, such as a feminine hygiene pad or a component thereof, the "z-direction" is the direction perpendicular / orthogonal to the xy-plane when laid flat on a horizontal surface. In the context of the manufacture or processing of a web of material, the term "z-direction" refers to the direction perpendicular to the xy-plane that is substantially occupied by the major surfaces of the web of material.

[0023] The terms "top," "bottom," "upper," "lower," "on," "under," "lower," "super-adjacent," "underlying," and similar terms relating to relative vertical position, as used herein to refer to a layer, component, or other feature of an absorbent article, such as a feminine hygiene pad, are relative to the z-direction and should be interpreted relative to the pad as it appears when placed flat on a horizontal surface, with the surface facing the wearer oriented upward and the surface facing outwardly oriented downward.

[0024] With respect to absorbent articles, such as feminine hygiene pads, or components or structures thereof, "wearer-facing" is a relative positional term that refers to a feature of the component or structure that, in use, is located closer to the wearer than another feature of the component or structure. For example, a topsheet has a wearer-facing surface that is located closer to the wearer than an opposite, outwardly facing surface of the topsheet.

[0025] With respect to absorbent articles, such as feminine hygiene pads, or components or structures thereof, "outwardly facing" is a relative positional term that refers to a feature of the component or structure that, in use, is located further from the wearer than another feature of the component or structure. For example, a topsheet has an outwardly facing surface that is located further from the wearer than an opposite wearer-facing surface of the topsheet.

[0026] As used herein with respect to absorbent articles, such as feminine hygiene pads or components thereof, "machine direction" or "MD" refers to the direction parallel to the flow of the article or component through processing / manufacturing equipment.

[0027] As used herein with respect to absorbent articles, such as feminine hygiene pads or components thereof, "cross direction" or "CD" refers to the direction perpendicular / orthogonal to the machine direction.

[0028] "Predominantly" and its aspects, when used to characterize a quantity of weight, volume, surface area, etc. of an absorbent article or component thereof that is constituted by a composition, material, feature, etc., means that a majority of such weight, volume, surface area, etc. of the absorbent article or component thereof is constituted by the composition, material, feature, etc.

[0029] General - Absorbent articles, feminine hygiene pads 1A, an absorbent article contemplated herein, such as a feminine hygiene pad 10, includes a wearer-facing surface and an opposing outwardly facing surface. A liquid permeable topsheet 20 may form at least a portion of the wearer-facing surface, and a liquid impermeable backsheet may form at least a portion of the outwardly facing surface. An absorbent core including an absorbent structure 40 may be disposed between the topsheet and the backsheet, and a fluid management layer 30 may be included and disposed between the absorbent structure 40 and the topsheet 20. (The fluid management layers described herein are sometimes known in the art as "acquisition / distribution layers," "distribution layers" or "secondary topsheets," and their purpose is to dissipate the energy from a fluid gush to the necessary extent, provide a temporary space volume for the expelled fluid to occupy during the time required for the underlying absorbent structure to take up and absorb the fluid, and distribute the fluid throughout the absorbent structure to maximize its effective utilization.) Non-limiting examples of absorbent articles sharing these characteristics include feminine hygiene pads (also known as "sanitary napkins," "menstrual pads," etc.), disposable incontinence pads, disposable incontinence undergarments, disposable baby diapers, and disposable baby / child training pants.

[0030] The topsheet 20 and the backsheet 50 may be joined together to form and define the perimeter of the pad 10. The absorbent structure 40 and the fluid management layer 30 are each sized to have an outer perimeter disposed laterally and longitudinally inward of the perimeter. The absorbent structure 40 and the fluid management layer 30 may be substantially similar or identical in size and shape to one another in the xy direction, or may each have different xy dimensions and / or shapes. One or both may be manufactured to have a rectangular shape as suggested in FIG. 1A, or one or both may be manufactured to have any other suitable shape, such as an oval shape, a stadium shape, a rounded rectangular shape, an hourglass shape, a peanut shape, etc. A shape with a concave contour along the longitudinal edges may provide enhanced comfort and / or conformity with the wearer's body in some instances.

[0031] The topsheet 20 may be joined to the backsheet 50 by attachment via any suitable attachment mechanism. The topsheet 20 and backsheet 50 may be directly joined to one another around the periphery of the article, or may be indirectly joined together by directly joining them to the absorbent structure 40, the fluid management layer 30, and / or additional layers disposed between the topsheet 20 and the backsheet 50. This indirect or direct joining may be accomplished by any suitable attachment mechanism known in the art. Non-limiting examples of attachment mechanisms may include, for example, fusion bonding, ultrasonic bonding, pressure bonding, adhesive bonding, or any suitable combination thereof.

[0032] Top sheet whole Generally, it is desirable for the topsheet 20 to be conformable, soft-feeling, and non-irritating to the wearer's skin. Suitable topsheet materials include liquid-permeable materials that are oriented toward and in contact with the wearer's body to allow bodily exudates to penetrate therethrough rapidly without fluids flowing back through the topsheet to the wearer's skin. The topsheet can allow for rapid movement of fluids therethrough while providing for the transfer or migration of the lotion composition therefrom to the surface facing the wearer's skin. The topsheet can be formed of or include a nonwoven material.

[0033] The nonwoven fibrous topsheet 20 may be manufactured by any known procedure for making nonwoven webs, non-limiting examples of which include spunbonding processes, carding, wet laying, air laying, meltblowing processes, needle punching, mechanical entanglement, thermomechanical entanglement, and hydroentanglement.

[0034] Nonwoven materials suitable for use as the topsheet may include one fibrous layer or may be a laminate of multiple nonwoven layers (e.g., spunbond-meltblown laminates) that may include the same or different compositions. In one specific example, the topsheet is a carded, air-through bonded nonwoven.

[0035] The topsheet contemplated herein does not include any major portion of the topsheet xy surface area occupied by a film. Some currently known topsheets for feminine hygiene pads include perforated films, such as hydroformed or vacuum-formed films, alone or in combination with adjacently disposed nonwoven web materials. The film may help prevent liquid from resurfacing to the surface and contacting the wearer. However, the inventors have found that a topsheet having the characteristics described herein, especially in combination with the fluid management layer described herein, can effectively prevent rewet as well as or better than a pad having a topsheet that includes a film over a major portion of the topsheet's xy surface area. Without wishing to be bound by theory, it is believed that by carefully selecting the fiber type and linear density of the fiber type in each layer within the fluid management layer, a desired combination of suitably short liquid acquisition time and low rewet can be obtained, overcoming the typical trade-off between these opposing objectives associated with conventional nonwoven topsheets. Improved performance is evident from the novel combination of a unique nonwoven topsheet with the fluid management layer of the present disclosure.

[0036] Basis weight In some examples, the nonwoven topsheet materials contemplated herein can be manufactured to have a basis weight of about 15 gsm to 80 gsm, more preferably about 20 gsm to 60 gsm, or most preferably about 20 gsm to 40 gsm (specifically, all values ​​within these ranges and any ranges created by them are recited). In a particular example, the topsheet nonwoven can be manufactured with a basis weight of about 18 gsm to 40 gsm, more preferably about 20 gsm to 30 gsm, and even more preferably about 22 gsm to 26 gsm (specifically, all values ​​within these ranges and any ranges created by them are recited). The desired basis weight range is influenced at the lower end of the range by the need for a level of web tensile strength required for processing, and by consumer preferences for opacity level and loft, feel and appearance substantiality. The desired basis weight range is influenced at the upper end of the range by the need for suitable rapid fluid acquisition and passage of fluid through the topsheet, as well as material cost issues.

[0037] Fiber Composition Non-limiting examples of woven and nonwoven materials suitable for use as the topsheet include fibrous materials made from natural fibers, such as cotton, including 100 percent organic cotton, modified natural fibers, semi-synthetic fibers (e.g., fibers spun from regenerated cellulose), synthetic fibers (e.g., fibers spun from polymeric resins), or combinations thereof. Synthetic fibers can include fibers spun from a single polymer or a mixture of polymers.

[0038] However, in some instances, it may be desirable for the nonwoven web of the topsheet to comprise less than 10 weight percent, more preferably less than 5 weight percent, even more preferably less than 1 weight percent of any combination of cotton fibers, other vegetable fibers, rayon fibers, or monocomponent fibers including polyester or polyamide. Such fibers are often hydrophilic in nature, which may cause the topsheet to tend to retain fluids rather than allowing them to pass to the absorbent component below. For the same reason, such fibers may cause the topsheet to tend to be easily rewetted.

[0039] Synthetic fibers may include monocomponent, bicomponent, or multicomponent fibers. (As used herein, bicomponent or multicomponent fibers are fibers having a cross-section divided into clearly identifiable component portions, each formed from a single polymer distinct from that of the other portions or a single homogenous mixture of polymers. Such fibers and processes for making them are known in the art. Examples of bicomponent fiber configurations having substantially circular cross-sections include side-by-side or "pie slice" configurations, eccentric sheath-core configurations, and concentric sheath-core configurations.

[0040] The nonwoven topsheets contemplated herein may include fibers with a myriad of combinations of component chemistries. For example, the fibers may be spun from thermoplastic polymeric materials such as polyethylene (PE) and / or polyethylene terephthalate (PET). The fibers may be spun in the form of bicomponent fibers. In some examples, bicomponent fibers may have a core component of a first polymer (e.g., PET) combined with another polymer as a sheath component in a sheath-core bicomponent configuration. In more specific examples, PE may combine with a PET core component to form a sheath component. Fibers including PET components may be selected to help provide the nonwoven web with loft and elasticity, and a resulting cushioned feel. Additionally, fibers including PET components with elasticity, if included, help the web retain the area and dimensions of the holes created therethrough.

[0041] Other polymeric materials may be included. For example, fibers spun from polypropylene, polyethylene, copolyethylene terephthalate, copolypropylene, and other thermoplastics may be included. It may be desirable to use a polymer with a lower melting temperature to form the sheath component of the sheath-core bicomponent fiber. Additionally, without being bound by theory, it is believed that the use of polyethylene terephthalate as the core component can help impart elasticity to the fiber and, therefore, to the topsheet.

[0042] Polyethylene, as a polymeric component from which fibers can be spun, has a relatively low melting temperature and exhibits a relatively smooth / silky surface feel compared to other potentially useful thermoplastic polymers. PET has a relatively high melting temperature and exhibits a relatively high stiffness and elasticity. Thus, in some embodiments, a sheath-core bicomponent topsheet nonwoven fiber may be desired, in which the sheath component is primarily polyethylene and the core component is primarily PET. Polyethylene is useful for imparting a silky feel to the fiber and thus the topsheet, and for enabling interfiber bonding by heat treatment that melts and fuses the sheaths of adjacent / contacting fibers at the lower melting temperature of polyethylene, while PET is useful for imparting elasticity and does not melt at the lower temperatures that melt PE in the heat treatment process. The inventors have found that a suitable weight ratio in such PE / PET sheath-core bicomponent fibers may be from about 40:60 to about 60:40.

[0043] Surface treatment (hydrophilic / hydrophobic) The surface of a fiber is either hydrophilic or hydrophobic in nature to varying degrees depending on its chemical composition. For example, the surface of fibers spun or otherwise formed from several types of polymers, such as polyethylene and polypropylene, is hydrophobic in nature. In contrast, the surface of other types of fibers, such as rayon fibers, is hydrophilic in nature. The surface of natural fibers can be hydrophilic or hydrophobic in nature, but this can depend on the treatment the fiber has undergone. For example, as-harvested cotton fibers have a coating of natural oils and / or waxes, and therefore their surface is hydrophobic. However, after they undergo processes including scouring and bleaching, the oils and / or waxes are removed and the fiber surface becomes hydrophilic.

[0044] Manufacturers and / or suppliers of spun synthetic staple fibers currently apply coatings in the form of surface finishes or processing aids to the fibers for the purpose of providing lubricity, for example, in the carding process. These surface finishes or processing aids can be formulated to be either hydrophobic or hydrophilic, and can be formulated to be substantially durable for purposes herein, in that they do not dissolve in aqueous fluids over the normal period of wear of the absorbent article. Thus, manufacturers or suppliers of spun synthetic staple fibers can provide fibers with either a hydrophobic or hydrophilic surface finish, and several manufacturers in the nonwoven materials industry currently do this.

[0045] Keeping in mind that spun synthetic staple fibers can be obtained with either inherently hydrophobic or hydrophilic surfaces, or with a surface finish that renders their surface hydrophilic or hydrophobic at the purchaser's option, it may be desirable to select fibers that have surfaces that are either hydrophilic ("hydrophilic fibers") or hydrophobic ("hydrophobic fibers"), or to select a mixture of both types of fibers.

[0046] In some examples, it may be preferred that the fibrous components of the topsheet are primarily, substantially, or completely hydrophobic by weight, or rendered hydrophobic by a fiber surface finish. A topsheet formed from a nonwoven web having a primarily hydrophobic fibrous component is resistant to rewet. On the other hand, if the size of the pores or interfiber voids in the fibrous structure of such a nonwoven web is not large enough, the topsheet may resist the passage of fluid from the wear-facing surface to the absorbent core component of the article underneath, i.e., it will not easily / rapidly acquire fluid, unless other features are included in combination as described herein.

[0047] In other instances, the fibers that make up some, most (by surface area), or all of the portion of the web material from which the topsheet is formed may be a mixture of both hydrophobic and hydrophilic fibers. In such instances, the hydrophilic fibers may help wick fluid from the wearer-facing surface of the topsheet to the absorbent core component below, while the hydrophobic fibers may help the topsheet resist rewet. The inventors have discovered that a good balance can be struck for such instances.

[0048] Thus, in some examples, the topsheet nonwoven may comprise a mixture of hydrophobic and hydrophilic fibers. For example, the nonwoven may comprise at least about 40 weight percent of the fibers, more preferably at least about 50 weight percent, or most preferably at least about 60 weight percent of the fibers (specifically including all values ​​within these ranges and any ranges created thereby). In more specific examples, the nonwoven topsheet may comprise about 40 weight percent to 70 weight percent, more preferably about 45 weight percent to 68 weight percent, or most preferably about 50 weight percent to 65 weight percent of the hydrophilic fibers (specifically including all values ​​within these ranges and any ranges created thereby). The topsheet nonwoven may comprise a mixture of hydrophilic and hydrophobic fibers in a weight ratio of hydrophilic fibers to hydrophobic fibers of 30:70 to 70:30, more preferably 35:65 to 65:35, and even more preferably 40:60 to 60:40. As mentioned above, the hydrophilicity of the hydrophilic fibers can be achieved by application of a surface treatment composition.

[0049] Without wishing to be bound by theory, it is believed that if the fibers are predominantly hydrophilic, in combination with other features described herein, this can improve fluid acquisition rate while not unduly impacting rewet in a negative or unacceptably negative manner. The opposite may be true if less rewet is the goal. In this situation, a higher weight fraction of hydrophobic fibers may be desired.

[0050] linear density Fibers are typically manufactured, selected, and purchased with a linear density specification, expressed as denier or decitex. For a fiber of a given polymer composition, linear density correlates with fiber size / diameter.

[0051] In some examples, the fibers making up the topsheet may be selected to have an average linear density of about 1.0 to 3.0 denier, more preferably about 1.5 to 2.5 denier, and even more preferably about 1.8 to 2.2 denier, with all combinations of subranges within these ranges being contemplated herein. Fibers having various linear densities within the ranges set forth above may be selected and included as well.

[0052] In some examples, the fibers comprising the topsheet may be selected to have an average linear density of about 3.0 to 5.0 denier, more preferably about 3.5 to 4.5 denier, and even more preferably about 3.8 to 4.2 denier, all combinations of subranges within these ranges being contemplated herein. It has been found that fibers selected within these ranges, in combination with other characteristics disclosed herein, may be considered to comprise a topsheet material of acceptable softness for many consumers, as well as offering other advantages over smaller fibers.

[0053] One advantage is that larger fibers generally provide larger inter-fiber / intra-web spaces or voids in the nonwoven web material, thereby providing larger pathways through which fluid may move more quickly through the nonwoven from the wearer-facing side to the outward-facing side (and thus to the absorbent component underneath the topsheet). Additionally, larger fibers of a given composition may be stiffer than smaller fibers of a similar composition, potentially compromising some surface "softness" properties, although greater fiber stiffness may also enhance a more resilient, bouncy, or cushiony feel to the topsheet nonwoven.

[0054] Staple fiber length Suitable fibers may be staple fibers having a length of at least about 30 mm, 40 mm, or 50 mm, up to about 55 mm, or from about 30 to 55 mm, or from about 35 to 52 mm, with ranges recited in 1 mm increments within the range. In a particular example, the staple fibers may have a length of about 38 mm.

[0055] hole The inventors have found that in topsheet nonwovens formed from fibers of relatively small size / linear density and / or fibers that are primarily, substantially, or completely hydrophobic, acquisition rates can be substantially increased by forming a pattern of holes through the web. In instances where the fibers are of relatively large size / linear density as also contemplated herein, forming and including a pattern of holes may not be considered necessary in some circumstances, but may be useful in other circumstances for the purpose of providing more inter-surface passageways of relatively large size and allowing discharged body exudates to pass more quickly downward through the topsheet.

[0056] Generally, the preferred holes have a size substantially larger than the average pore / void size in the nonwoven web. The holes can be formed by any suitable known pin punching process. The process can include the use of pins arranged in any desired pattern, extending radially from a cylindrical roller with pins and mated with a mating cylindrical roller with pin receiving holes in its surface. One or both rollers can be heated to a temperature sufficient to cause the nonwoven web fibers to soften and plastically deform without melting them. The passage of the nonwoven web material through the nip between these rollers can result in permanent or substantially permanent displacement of the position of the fibers in the nonwoven structure along the x- and y-directions and z-directions, thereby creating holes through the web that substantially retain their size and shape as the web is manipulated in subsequent / downstream processes such as winding, unwinding, and absorbent article manufacturing processes. Preferably, the hole-forming process is followed by bonding of the web by heat treatment to provide more reliable formation of more dimensionally and shape-stable holes.

[0057] An example of a portion of a topsheet nonwoven web material 500 having a pattern of holes 501 therethrough is shown in Figure 4. A magnified image of an example of holes through the nonwoven web material is shown in Figure 5. Holes are distinct from randomly positioned inter-fiber / intra-web spaces through the nonwoven web material in that they are created by a readily identifiable displacement of fibers along the xy directions, resulting in a concentrated grouping of displaced fibers that defines a perimeter of an opening in the z direction through the nonwoven web that is relatively larger than the randomly positioned pores or voids between the fibers that make up the material. Holes can be as small as 0.5 mm 2 ~2.5mm 2 , preferably about 0.6 mm 2 ~1.2mm 2can be produced through the web via processes and equipment configured to impart an average xy dimension hole area of ​​0.1 mm to 0.5 mm, and all combinations of subranges within these ranges are contemplated herein. Herein, the xy dimension area of ​​a hole is defined by the visually identifiable inner edge of the concentration of displaced fibers 503 around the hole. Escaped individual fibers (as an illustrative example, the stray individual fibers 504 shown in FIG. 5 ) that may escape the main structure and / or the concentration of displaced fibers around the hole and cross into or through the main opening area of ​​the hole are not considered to be subtracted from the hole area for purposes of this specification. Furthermore, without being bound by theory, it is believed that if the hole shape is too long, circular or too narrow, the rate of fluid acquisition may be adversely affected. Thus, it may be desirable for the hole to have a limited maximum average xy aspect ratio (maximum dimension in xy direction: minimum dimension). Thus, it may be desirable for the average aspect ratio of the holes to be about 2.5:1 to 1:2.5, more preferably about 1.5:1 to 1:1.5, or most preferably about 1:1, and all combinations of subranges within these ranges are contemplated herein. Furthermore, for the purpose of preserving the structural integrity of the web and the shape integrity of the holes, it is preferred that the xy-plane shape of most or all of the holes in at least the region of interest 25 ("ROI" defined below, see FIG. 1A), if not most or all of the topsheet, is a rounded shape without sharp corners (e.g., circular, oval, ovoid, elliptical, stadium, etc.). Thus, it may be desirable for the pinned roller used to create the holes to have pins that do not have sharp corners when viewed along a radially inward direction toward the axis of the roller.

[0058] Collectively, the pore area of ​​all pores in the portion of the topsheet of interest is the open xy planar area in the topsheet nonwoven ("open area"). To effectively mitigate potential obstacles to fluid acquisition that may result from finer denier fibers and / or configurations of fibers that are primarily hydrophobic, the inventors have identified a desired open area in combination with a desired average pore size. Thus, pores, if included, may be desired to collectively provide an open area of ​​between 6 percent and 25 percent, more preferably between 8 percent and 18 percent, and even more preferably between 10 percent and 15 percent, with all combinations of subranges within these ranges being contemplated herein. Such an amount of open area is preferably present throughout substantially the entire portion of the topsheet that covers the fluid management layer and / or absorbent structure, or at least in the region of interest 25 ("ROI") defined below (and see FIG. 1A). The lower limits of these ranges are imposed by the need for efficacy / performance, and pores should be provided with at least a minimum amount of open area to be effective as may be included for the purposes described herein. The upper ends of these ranges are imposed by the need for consumer acceptance: if the open area is too large, the consumer may perceive the topsheet as weak or of poor quality, and further, the topsheet will be less effective at retaining fluids beneath it and at hiding stains from absorbed fluids present in the absorbent component beneath the topsheet.

[0059] 1A, for purposes contemplated herein, the region of interest 25 ("ROI") is a rectangular portion of the topsheet having a longitudinal length of 60.0 mm, a lateral width of 30.0 mm, and centered at the longitudinal and lateral centers in the xy plane of the fluid management layer. The percent open area of ​​ROI 25 is the proportion of its xy area therein that is open in the z direction therethrough by the collective presence of holes 501 therein. Stated another way, the percent open area within an ROI is the proportion of the xy area of ​​holes in the ROI that is open in the z direction therethrough by the collective presence of holes 501 therein. 2 Divide by and multiply by 100%.

[0060] The percentage open area in the ROI can, in some instances, be obtained from specifications given to or provided by the manufacturer of the topsheet nonwoven web material. If this is not available, it can be measured via any suitable measurement technique that can be applied in a manner consistent with the above description of the xy dimension area of ​​the hole area and the description of "open area", which can include, but are not limited to, the hole open area measurement method described below.

[0061] join In general, the fibers forming the topsheet nonwoven are desirably bonded following the carding / fiber laydown process to give the web the necessary cloth-like structure and tensile strength (in both MD and CD) required for the web to substantially retain its structure in the form of a topsheet in downstream / subsequent processes and during use by the user / wearer. As an alternative to other bonding methods such as mechanical compression spot bonding (with or without application of heat energy), adhesive bonding, etc., bonding by air-through heating has been found to be effective in creating interfiber bonds and imparting structural integrity to the web while maintaining interfiber pore / void size and loft, imparting elasticity to the nonwoven. In an example of a suitable process, air heated to a selected heating temperature is blown and / or drawn (via vacuum) through the carded fibrous web as it is conveyed on a carrier belt along the machine direction through an oven or heating chamber. If the operating parameters, including the temperature and velocity of the heated air, as well as the exposure time, are appropriately adjusted, multiple randomly distributed interfiber bonds can be created within the fiber network, which imparts structural integrity to the web. When the constituent fibers are, for example, sheath-core bicomponent fibers in which the sheath component is a polymer having a melting temperature lower than that of the core component, the process can be configured such that fusion bonds are formed between the sheaths of adjacent contacting fibers without complete melting and loss of structure of the sheath, while the core remains unmelted in place. In such a process, bonds can be formed without the application of compression and thus without the attendant loss of caliper of the web and reduction in the size of the interfiber pores / voids.

[0062] Anti-sticking agent applied The absorbent article may include an anti-stick agent applied to at least a portion of the wearer-facing surface of the topsheet, the anti-stick agent comprising a polypropylene glycol material. The applied anti-stick agents described herein are believed to perform functions including reducing adhesion of menstrual fluid to the user's / wearer's skin and facilitating the transfer of menstrual fluid from the wearer-facing surface of the topsheet through it to the underlying fluid management layer and / or absorbent structure layer. Performing these functions can enhance the perception of cleanliness of the user's / wearer's skin and topsheet, especially after repeated discharge of menstrual fluid. Examples of suitable anti-stick agents and / or surfactants useful therein are disclosed in U.S. Patent Application Publication No. 2009 / 0221978 (wherein the composition is referred to as a "lotion") and U.S. Patent No. 8,178,748.

[0063] The anti-stick agent may comprise a polypropylene glycol ("PPG") material. In some examples, the anti-stick agent may consist essentially of a polypropylene glycol material, preferably a polypropylene glycol homopolymer such as polypropylene glycol, and optionally a carrier. In other examples, the anti-stick agent may comprise a polypropylene glycol material selected from the group consisting of a polypropylene glycol copolymer, a polypropylene glycol surfactant, and mixtures thereof. An anti-stick agent comprising a polypropylene glycol material may help reduce adhesion of menstrual fluid to the topsheet and, if the anti-stick agent is transferred to the user / wearer, reduce adhesion of fluid to the skin, thereby reducing soiling on the topsheet and reducing soiling on the skin. The anti-stick agent may also help improve the continuous fluid acquisition of the absorbent article.

[0064] The anti-stick agent may be applied to the wearer-facing surface of the topsheet 20 in any known manner and in any known pattern. For example, the anti-stick agent may be applied in a pattern of stripes or bands oriented in generally parallel longitudinal or transverse directions. It may be desirable to apply the anti-stick agent by spraying to avoid compressing or displacing any portion of the topsheet nonwoven or any three-dimensional features thereof. A substantially uniform spray application may be preferred.

[0065] The amount of anti-stick agent applied can vary and can be tailored to specific needs. For example, without being bound by theory, it is believed that the anti-stick agent can be applied at an effective level of at least about 0.1 gsm, 0.5 gsm, 1 gsm, 2 gsm, 3 gsm, 4 gsm, 5 gsm, 10 gsm, up to about 15 gsm, or up to about 12 gsm, or up to about 10 gsm. It is believed that the effectiveness is not further enhanced above these upper limits, and therefore application at basis weights above these upper limits may result in unnecessary use (waste) of anti-stick agent. The anti-stick agent can be applied within any subrange defined by any of the levels listed above (e.g., from about 0.1 gsm to about 15 gsm). These levels refer to the area of ​​the topsheet surface to which the anti-stick agent is actually applied. It may be preferred that most, substantially all, or all of the surface area of ​​the topsheet covering the fluid management layer and / or absorbent core has anti-stick agent applied. This is believed to be because the anti-stick agent may enhance the topsheet's ability to resist rewet.

[0066] The anti-stick agents contemplated herein provide significant advantages over other anti-stick agents, including non-PPG derived surfactants and other surface modifiers. This advantage may be considered particularly useful for feminine hygiene pads. Without being bound by theory, it is believed that the superior fluid handling properties of the PPG materials identified herein are a result of the way in which the PPG materials act on the solid components of menstrual fluid, as opposed to surface energy treatments that act on the water components of menstruation. Surface energy treatments may be less effective due to the presence of polar and dispersive components in menstrual fluid, which may inhibit the effectiveness of surface energy treatments. The PPG materials identified herein typically do not dissolve easily in menstrual fluid, and therefore can effectively coat surfaces without dissolving in the fluid, which provides a hydration barrier with electron donating dipoles that repel proteins with negative dipoles, thereby making menstrual fluid less likely to adhere to the surface of the article or to the skin of the wearer. Less adhesion of menstrual fluid to the wearer's skin and / or the topsheet promotes better and faster fluid transport through the topsheet, as well as fewer, smaller, and / or less visible stain patterns on the used product.

[0067] The PPG material identified herein can be applied as a component in an anti-stick agent or can be applied neat (i.e., the anti-stick agent consists of the PPG material). The PPG material, neat and / or as part of an anti-stick agent, can be applied at various amount levels depending on the desired fluid handling properties and the desired treatment of the wearer's skin. The PPG material can be applied to the outer surface of the topsheet in any pattern, such as a full coat, stripes or bands (oriented in the MD or CD direction), droplets, spiral patterns, and other patterns. The anti-stick agent including the PPG material, if present, can also be located near the channels or embossed areas.

[0068] The anti-sticking agent contemplated herein may comprise a PPG material. Suitable PPG materials for the purposes contemplated herein include PPG homopolymer materials, PPG copolymer materials, and PPG surfactant materials, and mixtures thereof. The anti-sticking agent may further comprise other optional ingredients. In one embodiment, the anti-sticking agent consists essentially of or consists of a PPG material, preferably polypropylene glycol. In another embodiment, the anti-sticking agent comprises a PPG material selected from the group consisting of polypropylene glycol copolymers, polypropylene glycol surfactants, and mixtures thereof.

[0069] Anti-stick agents contemplated herein may comprise PPG material at a level of about 0.1% to 100% by weight of the anti-stick agent. In some examples, the anti-stick agent may comprise less than about 10% PPG material by weight of the anti-stick agent, preferably about 0.5% to 8%, more preferably about 1% to 5% by weight of the anti-stick agent. In other examples, the anti-stick agent may comprise at least about 50% PPG material by weight of the anti-stick agent, preferably about 75% to 100%, more preferably about 90% to 100% by weight of the anti-stick agent.

[0070] Suitable PPG homopolymer materials may include those corresponding to the following formula:

[0071] [ka] in which R is hydrogen, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, benzyl, acetocarbonyl, propiocarbonyl, butyrocarbonyl, isobutyrocarbonyl, benzocarbonyl, fumarocarbonyl, aminobenzocarbonyl, carboxymethylene, aminopropylene, alkylated glucose, alkylated sucrose, alkylated cellulose, alkylated starch or phosphate, R is preferably hydrogen or methyl, - R1 is hydrogen, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, benzyl, acetocarbonyl, propiocarbonyl, butyrocarbonyl, isobutyrocarbonyl, benzocarbonyl, fumarocarbonyl, aminobenzocarbonyl, carboxymethylene, aminopropylene, alkylated glucose, alkylated sucrose, alkylated cellulose, alkylated starch or phosphate, R1 is preferably hydrogen or methyl, -n is 3 to 160, preferably 5 to 120, more preferably 10 to 100, and further more preferably 20 to 80.

[0072] Optionally, the PPG homopolymer may contain low levels of glycerol or butanediol as part of its monomer feedstock. If included, the preferred ratio of glycerol or butanediol to propylene glycol may be 1:1000 to 1:2, most preferably 1:100 to 1:5. The PPG homopolymer may have, but is not necessarily limited to, CAS numbers 25322-69-4, 25791-96-2, and 25231-21-4, the latter being most preferred.

[0073] Non-limiting examples of suitable PPG homopolymer materials include polypropylene glycol 4000, such as Pluriol P-4000 (BASF), Alkapol PPG-4000 (Alkaril Chemical) and Niax Polyol PPG 4025 (Union Carbide); polypropylene glycol 3500; polypropylene glycol 3000, such as Niax PPG 3025 (Union Carbide); polypropylene glycol 2000, such as Alkanol PPG-2000 (Alkaril Chemical) and Pluriol P-2000 (BASF), polypropylene glycol 1200, such as Alkapol PPG-1200 (Alkaril Chemical) and Glucam P-20 Humectant (Noveon); polypropylene glycol 1000, such as Niax PPG 1025 (Union Carbide); polypropylene glycol 600, such as Alkanol PPG-600 (Alkaril Chemical) and Glucam P-10 Humectant (Noveon); polypropylene glycol 400, such as Alkanol PPG-425 (Alkaril Chemical); polypropylene glycol 4000 glycerol ether, such as Pluriol T-4000 (BASF); polypropylene glycol 2000 glycerol ether, polypropylene glycol 2000 butanediol ether, polypropylene glycol 1500 glycerol ether, such as Pluriol T-1500 (BASF), polypolypropylene glycol 4000 and monoethyl ether, polypropylene glycol 2000 and dimethyl ether, polypropylene glycol 4000 and monobutyl ether, polypropylene glycol 2000 and monobuytyl ether, polypropylene glycol 1200 and dibutyl ether, polypropylene glycol 4000 and bis(2-aminopropyl ether), PPG-10 methyl glucose ether, and PPG-20 methyl glucose ether.

[0074] Suitable PPG homopolymer materials typically have a number average molecular weight of about 400 to 10,000, preferably about 600 to 6,000, and more preferably about 1,200 to 4,800.

[0075] Suitable PPG copolymer materials include those in which the polypropylene glycol segments are present as internal block components and / or as end block components of the copolymer structure. The following formulas illustrate the internal and end block components:

[0076] [ka] In the formula, x is 2 to 120, preferably 2 to 80, more preferably 3 to 60; y is 2 to 100, preferably 2 to 50, more preferably 3 to 30; R2 is hydrogen, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, benzyl, acetocarbonyl, propiocarbonyl, butyrocarbonyl, isobutyrocarbonyl, benzocarbonyl, fumarocarbonyl, aminobenzocarbonyl, carboxymethylene, aminopropylene, alkylated glucose, alkylated sucrose, alkylated cellulose, alkylated starch, or phosphate; R2 is preferably hydrogen, methyl, ethyl, isopropyl, or isobutyl.

[0077] Suitable polymers for forming propoxylated copolymers with PPG for the anti-stick agents of the present invention include homopolymers of alkyl methicones, phenyl methicones, dimethicones, alkyl trimethicones, phenyl trimethicones, polyols, polyethers (e.g., polyoxymethylene, polyoxyethylene and polyoxypropylene), polyimines, polyamides, polyacrylates, polyesters, and copolymers containing one or more of these polymeric units. Non-limiting examples of suitable polymers include polydimethylsiloxane, polyethylimine, polyacrylic acid, poly(ethylene-co-acrylic acid), polymethacrylic acid, poly(ethylene-co-methacrylic acid), poly(vinyl acetate), polyvinylpyrrolidone, poly(ethylene-co-vinyl acetate), poly(butanediol), poly(neopentyl glycol), poly(ethylene adipate), poly(butylene adipate), poly(ethylene glutamate), poly(butylene glutamate), poly(ethylene sebacate), poly(butylene sebacate), poly(ethylene succinate), poly(butylene succinate), poly(ethylene terephthalate), poly(butylene terephthalate), polycaprolactone, and polyglycerol.

[0078] Non-limiting examples of suitable PPG copolymer materials include PPG-12 dimethicone, e.g., Sisoft 910 (Momentive); bis-PPG-15 dimethicone / IPDI copolymer, e.g., Polyderm-PPI-SI-WI (Alzo); PPG / polycaprolactone block copolymer; PPG / polybutanediol / PEG triblock copolymer; polyethylimine / PPG copolymer, and polyacrylic acid-g-PPG graft copolymer.

[0079] Another suitable PPG material includes a PPG surfactant material, the following formula represents a suitable PPG surfactant material in which the PPG segment forms part of the head group:

[0080] [ka] In the formula, R3 is hydrogen, alkyl, alkylcarbonyl, alkyleneamine, alkyleneamide, alkylenephosphate, alkylenecarboxylic acid, alkylenesulfonate, and alkylenequat having a maximum of 6 carbon atoms, and R4 is octyl, nonyl, decyl, isodecyl, lauryl, myristyl, cetyl, isohexadecyl, oleyl, stearyl, isostearyl, tallow, linoleyl, jojoba, lanolin, behenyl, C24-C28 alkyl, C30-C45 alkyl, C40-C5 alkyl, C50-C6 alkyl, C60-C7 alkyl, C70-C8 alkyl, C80-C9 alkyl, C90-C10 alkyl, C100-C11 alkyl, C110-C12 alkyl, C120-C13 alkyl, C120-C14 alkyl, C120-C15 alkyl, C130-C14 alkyl, C140-C15 alkyl, C140-C15 alkyl, C150-C16 alkyl, C150-C17 alkyl, C150-C18 alkyl, C150-C20 alkyl, C150-C30 alkyl, C150-C40 alkyl, C150-C16 alkyl, C150-C20 alkyl, C150-C30 alkyl, C150-C40 alkyl, C150-C16 alkyl, C150-C20 alkyl, C150-C30 alkyl, C150-C40 alkyl, C150-C40 alkyl, C150-C5 ...30 alkyl, C150- wherein z is 1 to 100, preferably 2 to 30, and more preferably 3 to 25; and F is a functional group selected from the group consisting of an ether group (including oxy, glyceryl, glucose, sorbitan, sucrose, monoethanolamine, or diethanolamine), an ester group (including ester, glyceryl ester, glucose ester, sorbitan ester, or sucrose ester), an amine group, an amide group, and a phosphate ester group.

[0081] The following formula represents a suitable PPG surfactant material in which the PPG segments constitute the internal blocking groups:

[0082] [ka] In the formula, R5 is hexyl, 2-ethylhexyl, octyl, nonyl, decyl, isodecyl, lauryl, cocoyl, myristyl, cetyl, isohexadecyl, oleyl, stearyl, isostearyl, tallow, linoleyl, octylphenyl, or nonylphenyl; r is 1 to 120, preferably 4 to 50, and more preferably 6 to 30; and G is an ether, ester, amine, or amide bond.

[0083] Non-limiting examples of suitable PPG surfactant materials include PPG-30 cetyl ether, such as Hetoxol C30P (Global Seven); PPG-20 methyl glucose ether distearate, such as Glucam P-20 distearate emollient (Noveon), PPG-20 methyl glucose ether acetate, PPG-20 sorbitan tristearate, PPG-20 methyl glucose ether distearate, PPG-20 distearate, PPG-15 stearyl ether, such as Alamol-E (Croda-Uniqema) and Procetyl 15 (Croda), PPG-15 stearyl ether benzoate, PPG-15 isohexadecyl ether, PPG-15 stearate, PPG-15 dicocoate, PPG-12 dilaurate, PPG-11 stearyl ether, such as Varonic APS (Evonik); PPG-10 cetyl ether, such as Procetyl 10 (Croda); PPG-10 glyceryl stearate, PPG-10 sorbitan monostearate, PPG-10 hydrogenated castor oil, PPG-10 cetyl phosphate, PPG-10 tallowamine, PPG-10 oleamide, PPG-10 cetyl ether phosphate, PPG-10 dinonyl phenolate, PPG-9 laurate, PPG-8 dioctate, PPG-8 diethyl hexylate, PPG-7 lauryl ether, PPG-5 lanolin wax ether, PPG-5 sucrose cocoate, PPG-5 lanolin wax, PPG-4 jojoba alcohol ether, PPG-4 lauryl ether, PPG-3 myristyl ether, e.g. Promyristyl PM-3 (Croda), PPG-3 myristyl ether propionate, e.g. Crodamol PMP (Croda), PPG-3 benzyl ether myristate, e.g. Crodamol STS (Croda), PPG-3 hydrogenated castor oil, such as Hetester HCP (Alzo), PPG-3-hydroxyethyl soyamide, PPG-2 cocamide, PPG-2 lanolin alcohol ether, and PPG-1 coconut oil fatty acid isopropanolamide, such as Amizett IPC (Kawaken Fine Chemicals).A particularly preferred example of a suitable PPG material is PPG-15 stearyl ether, such as the product sold as CETIOL E by BASF Corporation (Florham Park, New Jersey, USA) and / or BASF SE (Ludwigshafen, Germany).

[0084] The anti-adherent agents contemplated herein may include a carrier at a total carrier concentration ranging from about 60% to 99.9%, preferably from about 70% to 99.5%, and more preferably from about 80% to 99% by weight of the anti-adherent.

[0085] Suitable carriers herein may include oils or fats, such as natural oils or fats, especially of vegetable or animal origin, or natural oil or fat derivatives. Non-limiting examples include avocado oil, apricot oil, apricot kernel oil, babassu oil, borage oil, borage seed oil, calendula oil, camellia oil, canola oil, carrot oil, cashew nut oil, castor oil, chamomile oil, cherry pit oil, chia oil, palm oil, cod liver oil, corn oil, corn germ oil, cottonseed oil, eucalyptus oil, evening primrose oil, grape seed oil, hazelnut oil, jojoba oil, juniper oil, kernel oil, linseed oil, macadamia oil, meadowfoam oil, and the like. Foam seed oil, menhaden oil, mink oil, moringa oil, mortierella oil, olive oil, palm oil, palm kernel oil, peanut oil, peach kernel oil, rapeseed oil, rosehip oil, safflower oil, sandlewood oil, sesame oil, soybean oil, sunflower oil, sunflower seed oil, sweet almond oil, tall oil, tea tree oil, turnip seed oil, walnut oil, wheat germ oil, zedoary oil, or hydrogenated derivatives thereof. Hydrogenated oils or fats of vegetable origin can include, for example, hydrogenated castor oil, peanut oil, soybean oil, turnip seed oil, cottonseed oil, sunflower oil, palm oil, kernel oil, linseed oil, corn oil, olive oil, sesame oil, cocoa butter, shea butter, and coconut oil.

[0086] Other non-limiting examples of fats and oils include butter, C12-C18 acid triglycerides, camellia oil, caprylic / capric / lauric triglyceride, caprylic / capric / linoleic triglyceride, caprylic / capric / stearic triglyceride, caprylic / capric triglyceride, cocoa butter, C10-C18 triglycerides, egg oil, epoxidized soybean oil, glyceryl triacetyl hydroxystearate, glyceryl triacetyl ricinoleate, glycosphingolipids, human placental lipids, hybrid safflower oil, hybrid sunflower seed oil, hydrogenated castor oil, hydrogenated castor oil laurate, hydrogenated coconut oil, hydrogenated cottonseed oil, hydrogenated C12-C18 triglycerides ... Liglycerides, hydrogenated fish oil, hydrogenated lard, hydrogenated menhaden oil, hydrogenated mink oil, hydrogenated orange roughy oil, hydrogenated palm kernel oil, hydrogenated palm oil, hydrogenated peanut oil, hydrogenated shark liver oil, hydrogenated soybean oil, hydrogenated tallow, hydrogenated vegetable oil, lanolin and lanolin derivatives, lanolin alcohol, lard, lauric / palmitic / oleic triglyceride, lesquerella oil, maleated soybean oil, meadowfoam oil, beef foot oil, oleic / linoleic triglyceride, oleic / palmitic / lauric / myristic / linoleic triglyceride, oleostearin, olive shell oil, omental lipids, orange roughy oil, pengawar jambi djambi oil, pentadesma butter, phospholipids, pistachio nut oil, placental lipids, rapeseed oil, rice bran oil, shark liver oil, shea butter, sphingolipids, tallow, tribehenin, tricaprin, tricaprylin, triheptanoin, trihydroxymethoxystearin, trihydroxystearin, triisononanoin, triisostearin, trilaurin, trilinolein, trilinolenin, trimyristin, trioctanoin, triolein, tripalmitin, tricebacin, tristearin, triundecanoin, vegetable oils, wheat bran lipids, etc., and mixtures thereof. A particularly preferred example of a suitable carrier is caprylic / capric triglyceride.This material is currently available, for example as MYRITOL 318, a product of BASF Corporation (Florham Park, New Jersey, USA) and / or BASF SE (Ludwigshafen, Germany).

[0087] Other suitable carriers may include mono- or diglycerides, such as mono- or diglycerides derived from saturated or unsaturated, linear or branched, substituted or unsubstituted fatty acids or fatty acid mixtures. Examples of mono- or diglycerides include mono- or di-C12-24 fatty acid glycerides, specifically mono- or di-C16-20 fatty acid glycerides, such as glyceryl monostearate and glyceryl distearate.

[0088] The carrier may also include esters of linear C6-C22 fatty acids and branched alcohols.

[0089] Carriers contemplated herein may also include sterols, phytosterols, and sterol derivatives. Sterols and sterol derivatives that may be used in the anti-adherent agents of the present invention include, but are not limited to, β-sterols having a tail at the 17-position and no polar group, such as cholesterol, sitosterol, stigmasterol, and ergosterol, as well as C10-C30 cholesterol / lanosterol esters, cholecalciferol, cholesteryl hydroxystearate, cholesteryl isostearate, cholesteryl stearate, 7-dehydrocholesterol, dihydrocholesteryl octyldecanoate, dihydrolanosterol, dihydrolanosteryl octyldecanoate, ergocalciferol, tall oil sterols, soybean sterol acetate, lanasterol, soybean sterol, avocado sterol, "AVOCADIN" (trade name of Croda Ltd, Parsippany, NJ), sterol esters and similar compounds, and mixtures thereof. A commercially available example of a phytosterol is GENEROL 122 N PRL purified soy sterols from Cognis Corporation (Cincinnati, Ohio).

[0090] Absorbent Core fluid management layer The absorbent core may include a fluid management layer 30 .

[0091] The fluid management layers contemplated herein may comprise a structured assembly of carded integrated fibers. The fluid management layers add caliper to the absorbent article and are typically compressible and may be constructed and structured to be elastic, which may impart a soft and / or "cushioned" feel to the article. Often, there is a trade-off between elasticity and softness when constructing layer components for absorbent articles. Softer (i.e., more compliant or pliable) materials may be less prone to recover their shape after deformation resulting from the application of force in one or more directions. The opposite may be true for elastic materials. Among the materials typically included as components of absorbent articles, elastic materials recover their original size and / or shape after deformation resulting from the application of force, but they may not be perceived as "soft" feeling. Additionally, many absorbent articles or their layer components may exhibit good elastic properties when dry, but upon absorbing liquid, their elasticity is substantially reduced. The absorbent articles contemplated herein exhibit good elastic properties in both dry and wet conditions.

[0092] In addition to the advantages of the flexibility and elasticity of the composition and structure for the fluid management layer contemplated herein, stain size control and faster fluid capture can be obtained.Stain size is important in the way absorbent articles are perceived by users.For feminine hygiene pads, if the stain visible on the pad after a period of use / wear is relatively large along the xy direction, the user may perceive the pad as approaching failure based on the appearance of the stain and its proximity to the periphery of the pad.In contrast, smaller stains can have a reassuring effect on the user / wearer by creating the perception that the pad is not approaching failure, since the edge of the stain is located substantially short of the periphery of the pad in the longitudinal and / or lateral directions.

[0093] The fluid acquisition rate of the pad may be considered important to the user / wearer as rapid acquisition can help the user / wearer feel dry and clean. If the pad requires a relatively long time to wick away fluid wicked from the topsheet, it may make the user feel wet and unclean.

[0094] As mentioned above, the fluid management layers 30 contemplated herein may be formed from a nonwoven material of integrated carded fibers. The fluid management layers contemplated herein may include one or more webs of carded fibers integrated with one another. When only a single carded web is included, the fibers of the single web may be integrated.

[0095] An endless variety of combinations of compositions, manufacturing methods, and configurations of the fluid management layer 30 may be designed and manufactured. However, in many situations, it may be desirable for the fluid management layer to have sufficient pore volume to allow for rapid capture / uptake of expelled fluids.

[0096] Multiple carded webs may be included to make up the fluid management layer and may differ from each other. For example, one carded web may have a different fiber component and / or mixture thereof than one or more of the others. For example, assuming a first carded web is closest to the wearer-facing surface in an absorbent article, the selection of the fiber components and manufacturing process of the first carded web may be configured such that the first web has a larger pore volume than one or more of the underlying carded webs of the fluid management layer. An underlying second or intermediate carded web may be included and similarly configured. In contrast, an underlying third or bottom carded web may be configured to draw fluids from the void spaces of the first and second carded webs and effectively distribute these liquid intrusions to or throughout the underlying absorbent structure. If the fiber configuration of one of the carded webs making up the fluid management layer is different from the fiber configuration of another carded web making up the fluid management layer (whether or not the fibers of the respective carded webs are integrated), the fluid management layer is considered herein to be of non-uniform configuration. Alternatively, if the carded webs that make up the fluid management layer all have the same fiber composition, the fluid management layer is considered herein to be of homogeneous composition.

[0097] After the fibers of the multiple carded webs that make up the fluid management layer are integrated, the respective carded webs cannot be easily separated. However, each carded web of the fluid management layer forms a stratum within a layer. Each layer can retain its unique properties for at least a portion of it along the z-direction even when its fibers are integrated with the adjacent / underlying carded web above. The fluid management layer can draw fluid through and from the topsheet via capillary action or wicking forces that are large enough to overcome any resistance to the passage of fluid through the topsheet or any attractive force the topsheet may have on the fluid that may exist as a result of the topsheet's composition and / or construction. The fluid management layer can also receive and contain a gush of fluid by providing a pore volume as a temporary reservoir along with a distribution function, allowing the absorbent structure time to efficiently utilize and take up and absorb the fluid.

[0098] Absorbent articles that exhibit soft cushioning feel, good elasticity, and fluid handling properties are contemplated herein. To impart these properties, the caliper of the fluid management layer may be considered important. In particular, typical calipers of webs from conventional spunlace lines achieve a caliper coefficient (caliper per 10 gsm basis weight) of 0.03 mm / gsm to 0.12 mm / gsm. In contrast, the fluid management layers contemplated herein may exhibit a caliper coefficient of at least 0.13 mm / gsm, at least about 0.15 mm / gsm, or about 0.2 mm / gsm (including any value within these ranges and any ranges created thereby). Fluid management layers contemplated herein may have a caliper factor of 0.13 mm / gsm to about 0.3 mm / gsm, or about 0.14 mm / gsm to about 0.25 mm / gsm, or about 0.15 mm / gsm to about 0.22 mm / gsm, including all values ​​within these ranges and any ranges created thereby. Caliper data is provided below for Prototype Sample 1 and Comparative Sample 1. The caliper and caliper factor of the fluid management layers of the present disclosure may be determined by the caliper and caliper factor test methods disclosed herein. It is important to note that the caliper factors discussed above are for calipers obtained using the caliper measurement method described below.

[0099] It has been discovered that a relatively simple process may be utilized to produce spunlaced webs to obtain increased caliper coefficients. Typically, the web path through the hydroentanglement line is tortuous, subjecting the web to both compressive and tensile stresses. This tortuous web path requires water jet pressures large enough to entangle the fibers to the extent necessary to impart sufficient tensile strength to the web to withstand subsequent processing. These water jets are typically directed at both sides of the web. The water pressure required to cause sufficient entanglement for web tensile strength is generally greater than that required to impart the desired fluid handling pore structure, and also causes a substantial reduction in the caliper of the resulting hydroentangled / spunlaced web. Additionally, since the web typically experiences significant z-direction compression and machine direction tensile stresses as it is conveyed along the various vacuum drums and rolls, the additional water jets can further entangle the constituent fibers of the layers. Further conveyance along the dryer drum subjects the web to additional z-direction compression and machine direction tensile forces on the dryer drum.

[0100] However, the inventors have discovered that by using a simplified web path that reduces radial compressive stress / excessive tension and by appropriate selection of fibers in the fluid management layer, the fluid management layer can retain the caliper of the web produced. To simplify the process, the use of rolls and the number of water jets utilized can be reduced. Although the resulting degree of fiber entanglement is not as great as that provided by conventional processes, by selecting the appropriate combination of fibers as disclosed herein, sufficient tensile strength can be imparted to the web, for example stiffening fibers that can be fusion bonded by a heat treatment process that causes fusion bonds between them where they contact each other. The simplified path and appropriate fiber selection as described herein allows manufacturers to impart caliper factors to fluid management layer web materials that have not been achieved before.

[0101] Importantly, the caliper coefficients of the prototype fluid management layer material samples manufactured as contemplated herein were derived from caliper data of the prototype material wound into rolls for storage and shipping. It is believed that caliper measurements of the same material could be made prior to such wrapping, resulting in an even higher caliper coefficient. However, such pre-wrapping caliper measurements may not necessarily be representative of the fluid management layer material actually used as a component of an absorbent article, which is typically wound into rolls for storage and shipping after manufacture.

[0102] Fluid management layers contemplated herein can have a basis weight of up to 75 grams per square meter (gsm), or a basis weight of up to 70 gsm, or a basis weight of about 30 gsm to 75 gsm, or more preferably about 45 gsm to 70 gsm, or even more preferably about 50 gsm to 65 gsm (including any value within these ranges and any ranges created thereby).

[0103] Some types of absorbent articles may not require a fluid management layer with a large basis weight as described above. For example, panty liners, which are generally not under the same demands as catamenial pads and do not have the same level of absorbency as catamenial pads, may be suitable to include a fluid management layer with a smaller basis weight compared to those described above. For example, the fluid management layer of a panty liner may be manufactured with a basis weight of about 20 gsm to 70 gsm, or about 35 gsm to 65 gsm, or even about 40 gsm to 60 gsm (specifically including all values ​​within these ranges and any ranges created thereby). In one specific example, the fluid management layer of the present disclosure may be manufactured with a basis weight of about 45 gsm to 55 gsm. The basis weight of the fluid management layer may be determined by the basis weight measurement method described below.

[0104] The inventors have also found that processing techniques can be used to create caliper in the fluid management layers not only for spunlace materials in which the layers are heterogeneous, but also for spunlace materials in which the layers are homogeneous, e.g., each layer has the same fiber composition. Additionally, the inventors have surprisingly found that spunlace materials produced by this process with appropriate fiber selection can also provide good elasticity and recovery from compression, along with improved fluid handling performance over spunlace materials produced by typical spunlace processes.

[0105] As a result of the fiber integration, no adhesives or binders need to be included in the material of construction of the fluid management layer to add sufficient tensile strength and / or stability. Additionally, the carded nonwoven fabrics of the fluid management layers contemplated herein may be manufactured from a variety of suitable fiber types that impart the desired performance characteristics. In the examples contemplated herein, the fluid management layer may include a combination of stiffening fibers, absorbent fibers, and elastic fibers.

[0106] Absorbent fibers may be included to impart to the fluid management layer the ability to absorb exuded fluids. Stiffening fibers may be included to serve to bond together upon heat treatment of the web, thereby imparting greater stiffness and elasticity to the fluid management layer. Elastic fibers may be included to impart an enhanced ability to the web to recover its shape and caliper after application of a compressive force.

[0107] To enhance the stabilizing effect of consolidation, crimped carded fibers may be included. One or more of the absorbent fibers, stiffening fibers, and elastic fibers may be crimped prior to consolidation. For example, when synthetic fibers are utilized, the fibers may be mechanically crimped by passing through a nip between a pair of rollers having interlocking teeth. The absorbent fibers may be mechanically crimped and / or may be given a chemically induced crimp.

[0108] The amount of absorbent fibers included may affect the ability of the fluid management layer to draw discharged fluid through and / or from the topsheet. However, as absorbent fibers absorb liquid, they tend to lose some of their structural integrity. The loss of structural integrity may reduce the elasticity of the fluid management layer, causing or exacerbating increased bunching and leakage. Thus, in principle, a relatively large proportion of absorbent fibers in the fluid management layer may be relatively more effective in quickly wicking discharged fluid away from the topsheet, but this may also result in other problems or drawbacks with the absorbent article, as discussed above.

[0109] Considering the potential problems associated with too high a proportion of absorbent fibers in the fluid management layer, the inventors have found that to balance the advantages and disadvantages identified above, a suitable weight fraction of absorbent fibers in the fluid management layer may be about 10 percent to 60 percent, more preferably about 15 percent to 50 percent, and even more preferably about 20 percent to 40 percent absorbent fibers (specifically including all values ​​within these ranges and any ranges created thereby). In one particular example, the fluid management layer may include about 20 percent to 30 percent absorbent fibers by weight. The weight fraction of absorbent fibers, elastic fibers, and / or stiffening fibers may be determined by the material composition analysis method disclosed below.

[0110] To mitigate the loss of structural integrity of the fluid management layer caused by wetting of the absorbent fibers, the fluid management layer may be comprised of an appropriate weight fraction of elastic fibers that enhance the ability of the fluid management layer to recover its shape and / or caliper after application of compressive loads imposed during use. Thus, the fluid management layer may be configured to include about 15 weight percent to 70 weight percent, or about 20 weight percent to 60 weight percent, or about 25 weight percent to 50 weight percent elastic fibers (all values ​​within these ranges and any ranges created thereby are specifically recited). In one specific example, the fluid management layer may include about 30 weight percent to 40 weight percent elastic fibers.

[0111] Stiffening fibers may be included to further enhance the elasticity of the fluid management layer and, consequently, the absorbent article. Following fiber blending, stacking, and laydown, the stiffening fibers in the precursor fiber stack may be bonded to one another via heat treatment of the fluid management layer material. This bonding of the stiffening fibers creates a support matrix that enhances the elasticity and stiffness of the fluid management layer. Thus, the fluid management layer may be comprised of about 25 weight percent to 70 weight percent, or about 30 weight percent to 60 weight percent, or even about 40 weight percent to 55 weight percent stiffening fibers (specifically, all values ​​within these ranges and any ranges created thereby are recited). In one specific example, the fluid management layer may include about 40 weight percent to 50 weight percent stiffening fibers.

[0112] If caliper, elasticity, and a soft cushioning feel are the objectives, the weight fraction of stiffening fibers can be greater than or substantially equal to the weight fraction of elastic fibers in the fluid management layer. The weight fraction of absorbent fibers can be less than the weight fraction of elastic and / or stiffening fibers. Generally, a higher weight fraction of absorbent fibers is believed to be beneficial for the rapid capture of fluids discharged from the topsheet, but it may be beneficial for the absorbent structure underneath the fluid management layer to draw fluids from the absorbent fibers when the absorbent fibers are placed close to the topsheet. If the weight fraction of absorbent fibers in the fluid management layer is relatively large, a relatively large absorbent structure underneath may be required to wick fluids away from the absorbent fibers in the fluid management layer. This generally imposes a higher material cost. Thus, the appropriate balance of absorbent fibers to stiffening fibers weight ratio may be selected to be about 1:7 to 2:1, or 1:4 to 1.5:1, or even 1:2 to 1:1 (specifically all values ​​within these ranges and any ranges created thereby are recited.) Similarly, the weight ratio of absorbent fibers to elastic fibers may be selected to be about 1:7 to 3:1, or 1:2 to 2:1, or even 1:1.5 to 1:1.

[0113] Regardless of whether the fluid management layer is included in an adult incontinence product, a menstrual product, a liner, or other hygienic article, the ability of the fluid management layer to acquire and draw liquid from the topsheet and wick the fluid to a location below the topsheet ensures that the user / wearer does not feel that the topsheet is wet at the time of discharge of the fluid. To achieve this, the inventors have found that the relatively increased caliper of the fluid management layer manufactured as discussed herein can enhance fluid acquisition through the relatively increased void volume of the fluid management layer. A relatively high caliper at a given basis weight equates to a relatively high void volume and higher permeability. Additionally, a relatively high caliper of the fluid management layer can also increase the level of opacity of the fluid management layer, thereby increasing the masking effect of fluid stains.

[0114] By carefully selecting the type of fibers that make up each layer within the fluid management layer, and selecting the linear density of the fibers (which correlates with fiber size), the desired objectives of suitably rapid acquisition and low rewet can be met. The fiber types of the individual layers are discussed below.

[0115] For purposes of this specification, references below to a "first" layer, a "second layer," etc. refer to the order of appearance of the layers from top to bottom, beneath the topsheet. The "first" layer is on top of the fluid management layers, closest to the topsheet, etc.

[0116] Suitable linear density values ​​(expressed in decitex units, or "dtex") of absorbent fibers for use in the fluid management layers contemplated herein are as follows: For example, the average linear density of the absorbent fibers may be selected to be about 1 dtex to 7 dtex, or about 1.4 dtex to 6 dtex, or even about 1.7 dtex to 5 dtex (specifically all values ​​within these ranges and any ranges created thereby are recited). In one specific example, the included absorbent fibers may be selected to have an average linear density of about 0.6 to 2.4 dtex, more preferably about 0.9 to 2.1 dtex, even more preferably about 1.1 to 1.9 dtex, and most preferably about 1.3 to 1.7 dtex. (The average decitex of absorbent, stiffening and elastic fibers may be determined by the fiber decitex method disclosed herein if this information is not known or available from the manufacturer or supplier.)

[0117] The absorbent fibers of the fluid management layer may have any suitable cross-sectional profile shape (the cross-section lies along a plane perpendicular to the longer dimension of the fiber's length when the fiber is straight). Some examples of suitable shapes may include trilobal, "H", "Y", "X", "T", round, or flat ribbon shapes. Additionally, the absorbent fibers may have a solid, hollow, or multi-hollow cross-section. Other examples of suitable multi-lobal absorbent fibers for use in the fluid management layers described herein are described in U.S. Patent Nos. 6,333,108, 5,634,914, and 5,458,835. The trilobal fiber shape may improve wicking and improve opacity and stain hiding properties. A suitable trilobal rayon fiber is available from Kelheim Fibres GmbH (Kelheim, Germany) and is sold under the trade name GALAXY. As mentioned above, each layer may include absorbent fibers of different shapes, although not all card processing machines may be suitable to handle such variations between / among the layers. In one specific example, the fluid management layer may include absorbent fibers having a round (circular) shape.

[0118] The absorbent fibers may comprise any suitable absorbent material. Some examples of absorbent fibrous materials include cotton, cellulosic (e.g., wood) pulp, rayon, or combinations thereof. In one example, the fluid management layer 30 may comprise viscose fibers.

[0119] The staple length of the absorbent fibers may be selected to be about 20 mm to 100 mm, or 30 mm to 50 mm, or even 35 mm to 45 mm (specifically all values ​​within these ranges and any ranges created by them are listed). Generally, the fiber length of wood pulp is about 4 to 6 mm, which is too short for use in conventional carding machines. Therefore, if wood pulp is desired as a fiber in the fluid management layer, additional processing may be required to mix and add the pulp to the carded web. In some examples, the pulp may be air-laid between the carded webs, and the combination may then be consolidated. As another example, tissue made from the pulp may be utilized in combination with the carded web, and the combination may then be consolidated.

[0120] As mentioned above, in addition to absorbent fibers, the fluid management layer of the present disclosure may include stiffening fibers. Stiffening fibers may be included to help provide structural integrity to the fluid management layer. Stiffening fibers may help increase the structural integrity of the fluid management layer in the machine direction and / or cross machine direction, which may facilitate easier web handling when processing the fluid management layer for incorporation into a disposable absorbent article.

[0121] Some examples of suitable linear density values ​​for the stiffening fibers are as follows: the stiffening fibers may be selected to be about 1.0 dtex to 6 dtex, or more preferably about 1.5 dtex to 5 dtex, or even more preferably about 2.0 dtex to 4 dtex (specifically all values ​​within these ranges and any ranges created thereby are recited). In certain examples, the stiffening fibers may be about 1.8 dtex to 2.6 dtex, or more preferably about 2.2 dtex.

[0122] Examples of suitable stiffening fibers may include bicomponent fibers comprising polyethylene and polyethylene terephthalate components or polyethylene terephthalate and copolyethylene terephthalate components. The components of the bicomponent fiber may be arranged in a sheath-core configuration, a side-by-side configuration, a concentric sheath-core configuration, an eccentric sheath-core configuration, a trilobal configuration, or other suitable configuration. In one specific example, the stiffening fiber may include a bicomponent fiber having polyethylene / polyethylene terephthalate components arranged in a concentric sheath-core configuration, where the sheath component comprises polyethylene.

[0123] Although other materials may be useful in bicomponent fibers with a sheath-core configuration, the inventors have found that the stiffness of the polyethylene terephthalate contained in the core component is useful for imparting elasticity to the structure. At the same time, the polyethylene component of the stiffening fiber, which has a relatively low melting temperature and is contained in the sheath component, can serve to bond the fibers together through heat treatment, and multiple randomly arranged interfiber bonds can be created throughout the structure. This can add tensile strength to the web in both the machine direction (MD) and cross machine direction (CD). Additionally, the bonds between the low melting point components of the stiffening fiber (e.g., polyethylene-PET sheath-core bicomponent fiber) create a matrix structure that tends to limit slippage between fibers, thereby increasing the elasticity of the material.

[0124] One of the advantages brought by the inclusion of stiffening fibers is that the integrated nonwoven fabric can be heat treated after the fiber entanglement process. As the weight fraction of stiffening fibers that make up the fluid management layer or layers increases, more inter-fiber bonds / connections are generated. Too many bonds / connections can make the fluid management layer too stiff for consumer acceptance, negatively affecting the user / wearer's perception of comfort and / or softness. Therefore, the selection of the weight fraction of stiffening fibers included in the fluid management layer can be considered important when designing an absorbent article.

[0125] In a heat stiffening process, the selection of the heating temperature may be influenced in part by the composition of the stiffening fibers, the design and operating parameters of the heating device, and the web processing speed (i.e., exposure time to the heating environment). To impart uniform stiffness across the fluid management layer, the heating device and operating parameters should be set to provide uniform heating to the fluid management layer web. Even small variations in temperature can substantially affect the formation of interfiber bonds between the stiffening fibers and the resulting tensile strength of the fluid management layer. An example of a suitable heat stiffening process that may be utilized is air-through heating, where air heated to a selected heating temperature is blown and / or drawn (via vacuum) through the web along a direction generally perpendicular to the larger plane defined by the web.

[0126] As mentioned above, the fluid management layer of the present disclosure may include elastic fibers. The inclusion of elastic fibers may help the fluid management layer maintain its permeability and shape and dimensional recovery after compression. Fibers of any suitable diameter may be utilized. For example, the elastic fibers may have a linear density (correlated with size / diameter) of about 4 dtex to 15 dtex, or about 5 dtex to 12 dtex, or even about 6 dtex to 10 dtex (specifically all values ​​within these ranges and any ranges created thereby are recited). In one specific example, the fluid management layer may include elastic fibers with variable cross-sections, e.g., round and hollow helices, and / or may include elastic fibers with variable decitex. In yet another specific example, the elastic fibers of the present disclosure may have about 10 decitex. The elastic fibers may be hollow.

[0127] The elastic fibers may be constructed / spun from any suitable thermoplastic, such as polypropylene (PP), polyethylene terephthalate (PET), or other suitable thermoplastics known in the art. Other suitable examples of elastic fiber components include polyester / coextruded polyester. Other suitable examples of elastic fibers may include bicomponent fibers, such as polyethylene / polypropylene, polyethylene / polyethylene terephthalate, polypropylene / polyethylene terephthalate, etc. These bicomponent fibers may be constructed as sheath and core. The utilization and inclusion of bicomponent fibers provides a cost-effective means of increasing the basis weight of the material while additionally allowing for optimization of the pore size distribution. The staple length of the elastic fibers may be selected to be about 20 mm to 100 mm, or about 30 mm to 50 mm, or even about 35 mm to 45 mm. The thermoplastic fibers may have any suitable structure or cross-sectional profile shape. For example, the thermoplastic fibers may be circular or may have other shapes, such as helical, wavy oval, trilobal, wavy ribbon, etc. Additionally, the included elastic fibers may be solid, hollow, or multi-hollow. The elastic fibers may be solid and have a round cross-sectional profile shape.

[0128] Optionally, the elastic fibers can be helical crimped or flat crimped. The elastic fibers can have a crimp value of about 4-12 crimps per inch (cpi), or about 4-8 cpi, or about 5-7 cpi, or about 9-10 cpi.

[0129] Specific non-limiting examples of elastic fibers may be obtained from Wellman International Ltd / Indorama Ventures, Mullagh, Kells Co. Meath, Republic of Ireland under the trade names H1311 and T5974. Other examples of elastic fibers suitable for use in the carded staple fiber nonwoven fabrics detailed herein are disclosed in U.S. Patent No. 7,767,598.

[0130] The stiffening fibers and the elastic fibers should be carefully selected. For example, the compositional chemical properties of the stiffening fibers and the elastic fibers or their components may be similar, but it may be desirable to select the composition of the elastic fibers so that their melting temperature is higher than that of the stiffening fiber composition. Otherwise, during heat treatment, bonds may form between the elastic fibers and the stiffening fibers, resulting in an overly stiff structure.

[0131] Within the gsm ranges disclosed herein, when the weight fraction of absorbent fibers in the fluid management layer exceeds about 30 percent, the elastic and / or stiffening fibers should be carefully selected. For a soft, cushioned fluid management layer having a caliper coefficient of at least 0.13 or more as described herein, the elastic and / or stiffening fibers can be selected to offset the loss of structural integrity of the absorbent fibers when wet. For example, a relatively high decitex elastic fiber can be useful to mitigate the loss of stiffness exhibited by the absorbent fibers when wet. In such an example, an elastic fiber having a linear density of about 5 dtex to 15 dtex, or about 6 dtex to 12 dtex, or even about 7 dtex to 10 dtex can be utilized.

[0132] Alternatively, or in combination, the stiffening fibers may be selected to further enhance structural integrity. For example, the stiffening fibers may include bicomponent fibers in a sheath-core configuration, where the sheath is co-polyethylene terephthalate (CoPET). However, such material changes may introduce additional problems. For example, bonding of materials in the fluid management layer may occur only via adhesives or bonding agents, as opposed to fusion bonding achieved by heat treatment.

[0133] In other examples, material selection and processes may be configured to provide more bonds between the stiffening fibers. If the absorbent fibers comprise more than about 30 weight percent of the fluid management layer, the heat and / or exposure time of the stiffening fibers may be increased. This may increase the number of bonds in the stiffening fiber matrix, thereby reducing the loss of stiffness of the absorbent fibers when wet. However, the increased number of bonds results in increased stiffness. The increased stiffness may reduce the perception of softness by the user.

[0134] Similarly, in addition or alternatively, when the absorbent fibers constitute about 30 weight percent or more, the linear density of the stiffening fibers can be increased to mitigate loss of stiffness of the absorbent fibers, in such instances, the linear density of the stiffening fibers can be selected to be about 3 dtex to 6 dtex, or about 4 dtex to 6 dtex.

[0135] Although it may seem that the solution to the "wet collapse" of the fluid management layer is simply to increase the linear density of the stiffening and / or elastic fibers, their selection and proportion should be balanced. Particularly for viscous fluids, the fluid management layer contemplated herein should have some degree of capillarity to help draw liquid away from the wearer-facing surface of the article. Including relatively high decitex fibers can have the advantage of caliper retention, but it can reduce capillarity, which reduces the ability of the fluid management layer to draw fluid away from the topsheet.

[0136] The fluid management layers contemplated herein may be incorporated into a variety of absorbent articles. A non-limiting example of a schematic diagram of an absorbent article in the form of a feminine hygiene pad contemplated herein is shown in FIG. 1A. As reflected, the pad 10 contemplated herein may include a topsheet 20, a backsheet 50, and an absorbent structure 40 disposed between the topsheet 20 and the backsheet 50. A fluid management layer 30 may be disposed between the topsheet 20 and the absorbent structure 40. The pad has a wearer-facing surface 60 and an opposite outwardly facing surface 62. The wearer-facing surface 60 is formed primarily by the topsheet 20, and the outwardly facing surface 62 is formed primarily by the backsheet 50. Additional components (not shown) may be included proximate the wearer-facing surface 60 and / or the outwardly facing surface 62. For example, if the absorbent article is an incontinence pad, a pair of barrier cuffs extending generally parallel to the longitudinal axis 100 of the pad 10 may form part of the wearer-facing surface 60. Similarly, one or more attachment fixing adhesives (used by the user / wearer to affix the pad in an appropriate position within an undergarment for use) may be present on the backsheet 50 and form part of the outwardly facing surface 62 of the absorbent article.

[0137] A non-limiting example of the configuration of the fluid management layer 30 is shown generally in Figure IB. As reflected, the fluid management layer 30 may have opposing edges 32A and 32B that may extend generally parallel to the lateral axis 200 and side edges 31A and 32B that may extend generally parallel to the longitudinal axis 100. Similarly, the absorbent structure 40 may have opposing edges 42A and 42B that may extend generally parallel to the lateral axis 200 and side edges 41A and 41B that may extend generally parallel to the longitudinal axis 100.

[0138] As reflected in the figure, each of edges 32A and 32B of the fluid management layer 30 may be disposed longitudinally outboard of the absorbent structure 40. However, this is not necessary. For example, edges 32A and / or 32B may be coextensive with the absorbent structure 40, or edges 32A and / or 32B may be disposed longitudinally inboard of edges 42A and / or 42B of the absorbent structure 40.

[0139] Similarly, side edges 31A and / or 31B may be located laterally outboard of side edges 41A and / or 41B of the absorbent structure 40. Alternatively, side edges 31A and / or 31B may be laterally coextensive with side edges 41A and / or 41B of the absorbent structure 40.

[0140] An arrangement of equipment along a manufacturing line configured to carry out a process for forming a fluid management layer of the present disclosure is shown diagrammatically in FIG. 2. As reflected, a plurality of carding machines 210, 220, and 230 may form carded webs 214, 224, and 234, respectively, which are deposited on a carrier belt 240 moving along the machine direction MD. Each of the carded webs 214, 224, and 234 may be provided to the carrier belt 240 via a chute 212, 222, 232, respectively. In general, a carding machine may have limitations on the volume and mass of fibrous material it can process and discharge at a desired production rate, and as a result, the carding machine may be subject to an upper limit on the basis weight of the carded fibrous web it can produce. Thus, for a relatively low basis weight / lower caliper fluid management layer, a single carding machine may be sufficient to lay down a stack of carded fibers to reach the desired basis weight at the desired production rate. For a larger desired basis weight / larger caliper fluid management layer, two, three, or more carding machines may be required to "stack" the carded webs of accumulated fibers to reach the desired basis weight, as suggested in Figure 2. After the first carded web 214 is deposited on the carrier belt 240, the second carded web 224 is deposited on / over the first carded web 214 on the carrier belt 240. Similarly, the third carded web 234 (if included) is deposited on / over the second carded web 224 and the first carded web 214 on the carrier belt 240.

[0141] One or more of the carded webs 214, 224, and 234 are then conveyed to a consolidation device 250, which may utilize either needles and / or high pressure water jets to entangle the fibers of the webs and consolidate them in the z-direction. Both carding and consolidation processes are known in the art.

[0142] Fewer than three or more than three card processing machines may be utilized in the process. For example, the fluid management layers contemplated herein may be manufactured utilizing only two card processing machines. In such an example, a first card processing web 214 is deposited onto a carrier belt 240. A second card processing web 224 is then deposited on / above the first card processing web 214. The first card processing web 214 and the second card processing web 224 are then combined as described herein.

[0143] Fluid management layers of various configurations can be manufactured using the arrangement of equipment shown diagrammatically in FIG. 2. However, the objective is that the fluid management layer has sufficient pore volume to allow rapid acquisition of fluid, and also be able to hold fluid away from the topsheet to reduce the possibility of rewetting. With these design objectives in mind, the fiber compositions of the carded webs, e.g., 214, 224, and / or 234, carded webs, can be selected to be different from each other. Assuming that the first carded web is located closest to the wearer-facing surface of the absorbent article, the fiber selection of the first carded web 214 can be such that there is more pore volume associated with this web. The second carded web 224 can be similarly configured. In contrast, the third carded web 234 can have a fiber composition adapted to draw fluid from the void spaces / pore volume of the first and second carded webs 214 and 224 and distribute the fluid to and throughout the absorbent structure. Alternatively, the first carded web 214, the second carded web 224, and the third carded web 234 may have a similar fiber composition.

[0144] A schematic diagram of a non-limiting example of a cross section through a plane along the z-direction of a fluid management layer contemplated herein is provided in FIG. 3. As shown, the fluid management layer 30 has a first surface 300a, which is the wearer-facing surface of the layer 30, and an opposing second surface 300b, which is the outwardly facing surface. Between the first surface 300a and the second surface 300b, the fluid distribution layer 30 may have two or more distinct layers 30a, 30b, 30c along the z-direction resulting from the successive laydown of carded webs. The layers may be broadly defined by fiber-integrated interface zones 30b, 30d, where the fibers of one carded web are integrated with the fibers of an adjacent or underlying carded web above by the process described above.

[0145] Examples of suitable fluid management layers (e.g., also known as "secondary topsheets" or "acquisition / distribution layers") are further described in U.S. Patent Application Nos. 16 / 831,862, 16 / 831,854, 16 / 832,270, 16 / 831,865, 16 / 831,868, 16 / 831,870, 16 / 831,879, and 17 / 490,193, and U.S. Provisional Patent Application No. 63 / 086,701. Additional suitable examples are described in U.S. Patent No. 9,504,613, WO 2012 / 040315, and U.S. Patent Application Publication No. 2019 / 0021917.

[0146] Absorbent Structure The absorbent structure 40 of the present disclosure may have any suitable shape, including, but not limited to, oval, stadium, rectangular, asymmetrical, peanut, trapezoid, rounded trapezoid, ovoid, and hourglass. In some examples, the absorbent structure 40 may have a contoured shape, for example, narrower in a mid-longitudinal region than in the end regions. As another example, the absorbent structure may have a tapered shape, tapering to a wider width at one end region of the pad and narrower width at the other end region of the pad. The absorbent structure 40 may have varying stiffness in the MD and CD directions.

[0147] The configuration and construction of the absorbent structure 40 may vary (e.g., the absorbent structure 40 may have varying caliper zones, hydrophilic gradients, superabsorbency gradients, or acquisition zones of lower average density and lower average basis weight). Additionally, the dimensions and absorbent capacity of the absorbent structure 40 may also be altered to accommodate different wearers. However, the total absorbent capacity of the absorbent structure 40 should be compatible with the design load and intended use of the disposable absorbent article or incontinence pad 10.

[0148] In some examples, the absorbent structure 40 may include multiple layers, each having a particular feature and / or function. In some examples, the absorbent structure 40 may include a wrap (not shown) that is included to encase the absorbent components of the absorbent structure. The wrap may be formed from one or more nonwoven materials, tissues, films or other materials, or laminates thereof. In one aspect, the wrap may be formed solely from a single material, substrate, laminate, or other material that is at least partially wrapped around itself.

[0149] The absorbent structure 40 may include one or more adhesives, for example, to help secure the SAP or other absorbent material within the first and second laminates.

[0150] Suitable absorbent structures comprising relatively large amounts of superabsorbent polymers ("superabsorbent polymers" - also known as "absorbent gelling materials" or "AGMs") having various core designs are disclosed in U.S. Pat. No. 5,599,335, EP 1 447 066, WO 95 / 11652, U.S. Patent Application Publication No. 2008 / 0312622(A1), and WO 2012 / 052172.

[0151] Additions to the absorbent structure are contemplated. Potential additions to the absorbent structure are described in U.S. Patent No. 4,610,678, U.S. Patent No. 4,673,402, U.S. Patent No. 4,888,231, and U.S. Patent No. 4,834,735. The absorbent structure may further comprise layers that mimic a dual core system, including a chemically stiffened fiber acquisition / distribution core placed on top of an absorbent storage core, as described in U.S. Patent No. 5,234,423 and U.S. Patent No. 5,147,345. These may be considered useful to the extent that they do not negate or compete with the effect of the laminate of the absorbent structure of the present invention described below.

[0152] Further examples of suitable absorbent structures 40 that can be used in the absorbent articles of the present disclosure are described in U.S. Patent Application Publication Nos. 2018 / 0098893 and 2018 / 0098891.

[0153] As mentioned above, the absorbent articles including the fluid management layer contemplated herein may include a storage layer. Referring back to Figures 1A and 1B, the storage layer is generally located in a position corresponding to the position where the absorbent structure 40 is depicted. The storage layer may be configured as described with respect to the absorbent structure. The storage layer may contain conventional absorbent materials. In addition to conventional absorbent materials such as creped cellulose wadding, carded cellulose fibers, rayon fibers, and ground wood pulp fibers (also known as airfelt or fluff pulp), and woven fibers, the storage layer may also include particles or fibers of superabsorbent materials that absorb fluids and form hydrogels. (Such materials are also known as absorbent gelling materials (AGMs).) AGMs are typically capable of absorbing and retaining a relatively large amount of body fluid per dry weight of AGM under moderate pressure. Synthetic fibers spun from polymers such as, for example, cellulose acetate, polyvinyl fluoride, polyvinylidene chloride, acrylic (such as ORLON), polyvinyl acetate, insoluble polyvinyl alcohol, polyethylene, polypropylene, polyamide (such as nylon), polyester, bicomponent fibers, tricomponent fibers, mixtures thereof, etc. The storage layer may also include a filler material, such as perlite, diatomaceous earth, vermiculite, or other suitable material, which can help reduce rewet variations.

[0154] The storage layer or fluid storage layer may include absorbent gelling material (AGM) in a uniform distribution throughout, or may include it in a non-uniform distribution. The AGM may be distributed and / or concentrated via deposition into channels or pockets, or may be deposited in a pattern, including stripes, crisscross patterns, swirls, dots, or any other two- or three-dimensional pattern that can be imagined. The AGM may be sandwiched between a pair of fibrous cover layers. The AGM may be at least partially encapsulated by a single fibrous cover layer.

[0155] A portion of the storage layer may be formed substantially solely of superabsorbent material / AGM or may be formed from AGM distributed and dispersed in a suitable carrier structure, such as a batt or pile of cellulosic fibers in the form of fluffed or stiffened fibers. One non-limiting example of a storage layer may include a first layer formed substantially solely of AGM particles or fibers, which is disposed or deposited on a second layer formed from a distribution of AGM particles or fibers within cellulosic fibers.

[0156] Examples of absorbent structures formed by layers of superabsorbent material / AGM and / or layers of superabsorbent material / AGM dispersed within a batt or other accumulation of cellulosic fibers that may be utilized in the absorbent articles contemplated herein (e.g., sanitary napkins, incontinence products) are disclosed in U.S. Patent Application Publication No. 2010 / 0228209 A1. Absorbent structures containing relatively large amounts of SAP / AGM with various core designs are disclosed in U.S. Patent No. 5,599,335, EP 1 447 066, WO 95 / 11652, U.S. Patent Application Publication No. 2008 / 0312622 A1, WO 2012 / 052172, U.S. Patent No. 8,466,336, and U.S. Patent No. 9,693,910 to Carlucci. These may be used to construct absorbent structures or storage layers.

[0157] Back sheet The backsheet 50 may be disposed under the absorbent structure 40 and will be the outermost layer of the article, forming the outwardly facing surface of the article. The backsheet 50 may be joined to the absorbent structure 40 and / or the topsheet (around the periphery) by any suitable attachment method known in the art. For example, the backsheet 50 may be secured to the absorbent structure 40 by a uniform continuous layer of adhesive, a patterned layer of adhesive, or an array of separate lines, spirals, or dots of adhesive. Alternatively, the attachment method may include the use of thermal bonding, pressure bonding, ultrasonic bonding, dynamic mechanical bonding, or any other suitable attachment method or combination of these attachment methods known in the art.

[0158] The backsheet 50 may be impermeable or substantially impermeable to liquids (e.g., urine, menstrual fluids) under normal conditions of use and may be fabricated from a thin plastic film, although other flexible liquid impermeable materials may be used. The backsheet 50 may prevent or at least inhibit exudates absorbed and contained in the absorbent structure 40 from wetting undergarments, outerwear, bedding, etc. that may be in contact with or in close proximity to the article 10. However, in some instances, the backsheet 50 may be configured to allow vapors to escape from the absorbent structure 40 (i.e., is "breathable"), while in some instances, the backsheet 50 may be configured to be vapor impermeable (i.e., non-breathable). The backsheet 50 may include a polymeric film, such as a polyethylene or polypropylene film. A suitable material for the backsheet 50 is, for example, a thermoplastic film having a thickness of approximately 0.012 mm (0.5 mil) to 0.051 mm (2.0 mil). Any suitable liquid impermeable backsheet known in the art may be utilized in the present invention.

[0159] The backsheet 50 functions as a barrier to prevent fluids absorbed and retained within the absorbent structure 40 from migrating to the outwardly facing surface of the pad. Preferred materials are soft, smooth, flexible, liquid and vapor permeable materials that provide softness and conformability for comfort, and are low noise so that movement does not create undesirable sounds.

[0160] Non-limiting examples of materials suitable for forming the backsheet are described in U.S. Patent Nos. 5,885,265, 6,462,251, 6,623,464, and 6,664,439. Examples of suitable bilayer or multilayer breathable backsheets include those described in U.S. Patent Nos. 3,881,489, 4,341,216, 4,713,068, 4,818,600, European Patent Nos. 203 821, 710 471, 710 472, and 793 952. Further examples of suitable single layer breathable backsheets include those described in GB-A2184 389, GB-A2184390, GB-A2184391, U.S. Pat. Nos. 4,591,523, 3 989 867, 3,156,242, and WO 97 / 24097.

[0161] The backsheet may be a nonwoven web having a basis weight of about 20 gsm to 50 gsm. In one embodiment, the backsheet may be a hydrophobic 23 gsm spunbond nonwoven web of 4 denier polypropylene fibers available from Fiberweb Neuberger under the trade designation F102301001. The backsheet may be coated with an insoluble liquid swellable material as described in U.S. Patent No. 6,436,508.

[0162] The backsheet has an outwardly facing side and an opposite wearer facing side. The outwardly facing side of the backsheet may include non-adhesive areas and adhesive areas. The adhesive areas may be provided by any conventional means for the purpose of allowing the user / wearer to affix the pad to the wearer facing surface of the undergarment in a suitable position for use. Pressure sensitive adhesives have been found to work well for this purpose.

[0163] Experimental Example For purposes of experimentation and discovery, the inventors have manufactured and tested a large number of prototype samples of absorbent articles in the form of feminine hygiene pads comprising various configurations of topsheets and fluid management layers as contemplated herein. The prototype samples had the following characteristics:

[0164] Top sheet The topsheets of all prototype samples had a basis weight of about 24 gsm.

[0165] Topsheets for all prototype samples were cut from a nonwoven web of carded staple filaments having an average staple length of 38 mm and an average denier of 4. The fibers were bicomponent with a concentric sheath-core configuration where the core component was PET and the sheath component was low density polyethylene (LDPE) with a weight ratio of the components being approximately 1:1. The nonwoven web contained a plurality of randomly distributed interfiber bonds created by through-air thermal bonding of the carded fibers.

[0166] The topsheet was affixed to the underlying fluid management layer via application of a pressure sensitive adhesive applied in a series of discrete narrow spiral paths generally oriented longitudinally, which in turn was affixed to the underlying absorbent structure in a similar manner.

[0167] Further details varied from sample to sample as specified below.

[0168] Sample #1: The topsheet nonwoven was formed from a blend of hydrophilic and hydrophobic fibers with a ratio of the weight of hydrophilic fibers to the weight of hydrophobic fibers of 60: 40. The topsheet nonwoven did not contain any holes or anti-stick agents applied.

[0169] Sample #2: The topsheet nonwoven was formed from a blend of hydrophilic and hydrophobic fibers with a ratio of hydrophilic fiber weight to hydrophobic fiber weight of 60:40. The topsheet nonwoven was 0.55 mm 2and contained a pattern of holes having an average xy dimension hole area of ​​approximately 6 percent open area. The topsheet nonwoven did not have an anti-stick agent applied.

[0170] Sample #3: A topsheet nonwoven was formed from a blend of hydrophilic and hydrophobic fibers with a ratio of hydrophilic to hydrophobic fibers by weight of 60:40. The nonwoven contained a regular pattern of holes therethrough, the holes being 0.60 mm 2 , constituting approximately 12 percent open area. The topsheet nonwoven did not have an anti-stick agent applied.

[0171] Sample #4: A topsheet nonwoven was formed from a blend of hydrophilic and hydrophobic fibers with a ratio of hydrophilic to hydrophobic fibers by weight of 60:40. The nonwoven had a regular pattern of holes therethrough, the holes being 2.3 mm in diameter. 2 , constituting about 19 percent open area. The topsheet nonwoven did not have an anti-stick agent applied.

[0172] Sample #5: The topsheet nonwoven was formed substantially entirely from hydrophobic fibers. The topsheet nonwoven did not contain any holes or applied anti-stick agents.

[0173] Sample #6: The topsheet nonwoven was formed substantially entirely from hydrophobic fibers. The nonwoven had a regular pattern of holes therethrough, the holes being 0.55 mm 2 , constituting about 6 percent open area. The topsheet nonwoven did not have an anti-stick agent applied.

[0174] Sample #7: The topsheet nonwoven was formed substantially entirely from hydrophobic fibers. The nonwoven had a regular pattern of holes therethrough, the holes being 0.6 mm or smaller. 2 and comprising about 12 percent open area. The topsheet nonwoven did not have an anti-stick agent applied.

[0175] Sample #8: The topsheet nonwoven was formed substantially entirely from hydrophobic fibers. The nonwoven had a regular pattern of holes therethrough, the holes being 2.3 mm 2 and comprising about 19 percent open area. The topsheet nonwoven did not have an applied anti-stick agent.

[0176] fluid management layer All prototype samples included a fluid management layer of substantially common structure and composition disposed under the topsheet. The common fluid management layer had a basis weight of about 65 gsm. It was composed of about 20 weight percent viscose fiber of 1.3 dtex, about 30 weight percent hollow spiral polyethylene terephthalate fiber of 10 dtex, and about 50 weight percent bicomponent fiber of 2.2 dtex having a concentric sheath-core configuration, the core component being PET and the sheath component being PE, with a weight ratio of PET:PE of about 1:1. These bicomponent fibers had an average decitex of about 2.2. The fluid management layer had two layers, each with the same homogeneous fiber blend, lightly hydroentangled and air-through thermally bonded.

[0177] Absorbent Structure All prototype samples included an absorbent structure of substantially common structure and composition disposed beneath a fluid management layer. The common absorbent structure was an airlaid mixture of pulp fibers, absorbent gelling material, and bicomponent fibers, had a basis weight of 182 gsm, and was available prefabricated in festooned web form from Glatfelter Corporation (Charlotte, North Carolina, USA). The structure and composition of the absorbent structure are not believed to play a significant role in the performance differences measured between the various prototype samples.

[0178] Back sheet All prototype samples included a common backsheet formed from a sheet of extruded polyethylene film, positioned beneath the absorbent structure.

[0179] Test Results and Data The mass of all eight prototype samples was measured and tested using the acquisition time and rewet measurement methods set forth below.

[0180] Figure 9 reports the measured second acquisition time (ACQ-2) for each of the eight samples. For the purposes of this specification, the second acquisition time (ACQ-2) is considered to be most relevant to the actual user experience, as it reflects the fluid acquisition of a feminine hygiene pad that has been used / worn for a period of time, absorbed some fluid, but is then subjected to a relatively higher fluid discharge, such as may occur with a sudden change in the user's / wearer's body position following a period of inactivity or relatively low activity. The thick horizontal line drawn at the 30 second mark in the chart represents what the inventors consider to be the longest acquisition time acceptable to the relevant consumer / user.

[0181] Figure 10 reports the measured surface free fluid (SFF) and rewet total for each of the eight samples. For the purposes of this specification, this total is considered to be most relevant to the actual user experience, as it reflects the extent to which a pad that has absorbed a significant amount of fluid allows the fluid to return to the surface of the topsheet under moderate pressure, which reflects the cause of unsatisfactory wetness sensation for the user / wearer. The thick horizontal line drawn at the 400 milligram mark in the chart represents what the inventors consider to be the highest SFF+rewet that is acceptable to the relevant consumer / user.

[0182] From the plot in Figure 9, it can be seen that all prototype samples exhibited second acquisition times that were deemed acceptable. Prototype samples 1-4 exhibited the best performance, with prototype sample 3 exhibiting the best performance of all.

[0183] From the chart in Figure 10, it can be seen that all prototype samples exhibited SFF+rewet values ​​that were deemed acceptable. Prototype Sample 1 performed the best of all, followed by prototype samples 8, 7, and 5, in that order.

[0184] From this data, it can be concluded that Prototype Sample 1 was the most successful as it placed within the top four in both categories. However, in various situations, product designers may choose to prioritize quick acquisition (e.g., Prototype Sample 3 was the best performing of the samples tested), or alternatively, low rewet values ​​(e.g., Prototype Sample 1 was the best performing of the samples tested).

[0185] Test and Measurement Methods Caliper The caliper or thickness of a test specimen is measured as the distance between a reference platform on which the specimen rests and a footrest that exerts a specified amount of pressure on the specimen for a specific period of time. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, and test specimens are conditioned in this environment for at least two hours prior to testing.

[0186] Caliper is measured with a manual micrometer equipped with a foot press capable of applying a constant pressure of 0.50 kPa ± 0.01 kPa to the test specimen. The manual micrometer is a dead weight instrument with an accurate reading to 0.01 mm. A suitable instrument is a Mitutoyo Series 543 ID-C Digimatic available from VWR International, or equivalent. The foot press is a flat grounded circular movable surface having a diameter smaller than the test specimen and capable of applying the required pressure. A suitable foot press has a diameter of 25.4 mm, although smaller or larger foot presses can be used depending on the size of the specimen being measured. The test specimen is supported by a horizontal flat reference platform larger than and parallel to the surface of the foot press. The system is calibrated and operated according to the manufacturer's instructions.

[0187] If necessary, obtain the test specimen by removing it from the absorbent article. When cutting the test specimen from the absorbent article, care is taken not to contaminate or deform any of the layers of the test specimen in the process. The test specimen is obtained from an area that does not contain folds or wrinkles and should be larger than the presser foot.

[0188] To measure the caliper, first zero the micrometer against a horizontal flat reference platform. Place the test specimen on the platform with the test location centered under the foot presser. Gently lower the foot presser at a downward speed of 3.0 mm ± 1.0 mm / sec until full pressure is applied to the test specimen. After waiting 5 seconds, record the caliper of the test specimen to the nearest 0.001 mm. Repeat similarly for a total of 10 replicate test specimens. Calculate the arithmetic mean of all caliper measurements and report as caliper to the nearest 0.001 mm.

[0189] Caliper factor Caliper factor, as stated above, is the caliper per 10 gsm of basis weight of the sample. Therefore, the formula is caliper / (basis weight / 10).

[0190] Basis weight The basis weight of a sample of a sheet or web material is the mass in grams per unit area in square meters of a single layer of material. If not otherwise known or available, basis weight may be measured using EDANA Official Method NWSP 130.1. A block of test sample is cut to a known area and an analytical balance accurate to 0.0001 grams is used to determine the mass of the sample. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity, and test samples are conditioned in this environment for at least 2 hours prior to testing.

[0191] Measurements are made on test samples taken from rolls or sheets of raw material or from layers of material excised from absorbent articles. When the layers of material are excised from the absorbent article, care is taken not to contaminate or deform the sample layers in the process. The excised layers should be free of residual adhesive. To ensure that all adhesive is removed, the layers are immersed in a suitable solvent that will dissolve the adhesive without adversely affecting the material itself. One such solvent is THF (general purpose tetrahydrofuran, CAS 109-99-9, available from any convenient source). After solvent immersion, the layers of material are allowed to air dry thoroughly in a manner that prevents unwanted stretching or other deformation of the material. After the material is dry, the test specimen is obtained. The test specimen should be as large as possible to allow for any inherent material variations to be taken into account.

[0192] Measure the dimensions of the single ply test specimen using a calibrated steel metal ruler or equivalent that is traceable to NIST. Calculate the area of ​​the test specimen and record it to the nearest 0.0001 square meter. Obtain the mass of the test specimen using an analytical balance and record it to the nearest 0.0001 grams. Calculate the basis weight by dividing the mass in grams by the area in square meters and record it to the nearest 0.01 grams per square meter (gsm). Repeat the test in the same manner for a total of ten replicate test specimens. Calculate the arithmetic average of the basis weight and report it to the nearest 0.01 grams per square meter.

[0193] Material composition analysis When no other information is available, the quantitative chemical composition of test specimens containing mixtures of fiber types is determined using ISO 1833-1. All measurements are performed in a laboratory maintained at 23°C ± 2°C and 50% ± 2% relative humidity.

[0194] The analysis is performed on test samples taken from rolls or sheets of raw material or from layers of material excised from absorbent articles. When the layers of material are excised from the absorbent article, care is taken not to contaminate or deform the sample layers in the process. The excised layers should be free of residual adhesive. To ensure that all adhesive is removed, the layers are immersed in a suitable solvent that will dissolve the adhesive without adversely affecting the material itself. One such solvent is THF (general purpose tetrahydrofuran, CAS 109-99-9, available from any convenient source). After solvent immersion, the layers of material are allowed to air dry thoroughly in a manner that prevents unwanted stretching or other deformation of the material. After the material is dried, test specimens are obtained and tested according to ISO 1833-1 to quantitatively determine its chemical composition.

[0195] Average fiber decitex (dtex) or denier Textile webs (e.g., woven, nonwoven, airlaid) are composed of individual fibers of material. The fibers are characterized in some respects by their linear mass density, reported in units of denier or decitex. The decitex value is the mass in grams of that fiber present in 10,000 meters of fiber. The denier value is the mass in grams of that fiber present in 9,000 meters of fiber. The average decitex or denier value of the fibers in a material web is often reported by the manufacturer as part of a specification. If the average decitex or denier value of the fiber is not otherwise known or available, it can be calculated by measuring the cross-sectional area of ​​the fiber by suitable microscopy, such as scanning electron microscopy (SEM), determining the composition of the fiber using suitable techniques, such as FT-IR (Fourier Transform Infrared) spectroscopy and / or DSC (Dynamic Scanning Calorimetry), and then calculating the mass of fiber in grams present in 10,000 meters of fiber (for decitex) or 9,000 meters of fiber (for denier) using literature values ​​for the density of the composition.

[0196] All tests are performed in a room maintained at a temperature of 23°C ± 2.0°C and a relative humidity of 50% ± 2%, and samples are conditioned under the same environmental conditions for at least two hours prior to testing.

[0197] If desired, a representative sample of the web material of interest can be cut from the absorbent article, where the web material is cut in a manner that does not stretch, distort, or contaminate the sample.

[0198] SEM images are acquired and analyzed as follows to determine the cross-sectional area of ​​the fibers. To analyze the cross-section of a sample of web material, a test specimen is prepared as follows: A specimen approximately 1.5 cm (height) by 2.5 cm (length) without any folds or wrinkles is cut from the web. The specimen is immersed in liquid nitrogen and an edge is broken off along the length of the specimen using a razor blade (VWR Single Edge Industrial Razor blade No. 9, surgical carbon steel). The specimen is sputter coated with gold and then attached to an SEM mount using double-sided conductive tape (Cu, 3M available from electron microscopy sciences). The specimen is oriented so that the cross-section is as perpendicular as possible to the detector to minimize any oblique distortion of the cross-section being measured. SEM images are acquired with sufficient resolution to clearly show the cross-sections of the fibers present in the specimen. Fiber cross-sections vary in shape, with some fibers being composed of multiple individual filaments. Regardless, the area of ​​each of the fiber cross sections is determined (e.g., diameter for round fibers, major and minor axes for elliptical fibers, and using image analysis for more complex shapes). If the fiber cross sections exhibit a heterogeneous cross-sectional composition, the area of ​​each discernible component is recorded and the dtex contribution for each component is calculated and then summed. For example, if the fiber is a bicomponent fiber, the cross-sectional area is measured separately for the core and sheath, and the dtex contributions from the core and sheath, respectively, are calculated and summed. If the fiber is hollow, the inner part of the fiber, consisting of air, which does not contribute significantly to the dtex of the fiber, is excluded from the cross-sectional area. Overall, at least 100 such measurements of cross-sectional area are made for each fiber type present in the specimen, and the area in square micrometers (μm 2 ) is the arithmetic mean of the cross-sectional area a k to 0.1 μm 2 Record in units.

[0199] The fiber composition is determined using common characterization techniques such as FTIR spectroscopy. For more complex fiber compositions (such as polypropylene core / polyethylene sheath bicomponent fibers), a combination of common techniques (e.g., FTIR spectroscopy and DSC) may be required to fully characterize the fiber composition. This process is repeated for each fiber type present in the web material.

[0200] The average decitex of each fiber type in the web material k The value is calculated as follows: d k =10000m×a k ×ρ k ×10 -6 In the formula, d k is in grams (per 10,000 meters of calculated length), and a k The unit is μm 2 and ρ k The unit is grams per cubic centimeter (g / cm 3 ) The average decitex is reported along with the fiber type (e.g., PP, PET, cellulose, PP / PET bicomponent) in 0.1 g increments (per 10,000 meters of calculated length). The average denier of each fiber type in the web material is its decitex d k value × 0.9.

[0201] Pore ​​percent opening area measurement method The percent open area is measured on an image of the perforated topsheet test specimen acquired using a flatbed scanner. The scanner can scan in reflectance mode with a resolution of 2400 dpi and 8-bit grayscale. A suitable scanner is an Epson Perfection V750 Pro manufactured by Epson America Inc. (Long Beach, California, USA), or one with substantially similar functionality. The scanner is connected to a computer running an image analysis program. A suitable program is ImageJ v.1.47 (National Institute of Health, USA), or one with substantially similar functionality. The specimen image is distance calibrated against an image of a NIST certified ruler acquired. To allow for maximum contrast, the specimen is backed with a uniform black opaque background sheet prior to image acquisition. All measurements are performed in a conditioned room maintained at about 23±2°C and about 50±2% relative humidity.

[0202] The measurement sample is prepared as follows.

[0203] Obtain the required number of samples of the absorbent article of interest. To obtain the measurement specimen, the sample absorbent article is taped around its periphery (i.e., not taped in the area where the fluid management layer is underneath) with the side facing the wearer up and in a flat configuration on a horizontal, flat work surface. If present, any elastic material included (e.g., in the leg cuffs) can be cut to facilitate laying the article flat. The outer border of the area of ​​the perforated topsheet that covers the fluid acquisition layer of the article is identified and marked. Then, with a new razor blade or other equivalent new sharp cutting instrument, cut the topsheet and any attached underlayer around and through this marked outer border. Then, carefully separate and remove the test specimen of the perforated topsheet from the underlying layer from this cut-out portion, such that its longitudinal and lateral dimensions do not change to avoid distortion of the holes. If the top sheet is attached to the underlayer via an adhesive, before attempting separation, apply any solvent suitable for dissolving the adhesive and allowing easy separation of the top sheet from the underlayer without dissolving the polymeric material of the fibers that make up the top sheet nonwoven web material. (In many instances, tetrahydrofuran (THF) can be a suitable solvent for this purpose. It does not matter whether the solvent dissolves the surface finish coating applied on the fibers, as long as it does not dissolve the polymer that makes up the fibers themselves.) Once the cut-out portion of the top sheet that constitutes the measurement specimen is removed, identify its wearer-facing side. Five replicate measurement specimens obtained from five samples of the absorbent article of interest are prepared for measurement. The specimens are conditioned for 2 hours at about 23°C ± 2°C and about 50% ± 2% relative humidity before imaging.

[0204] The image is obtained as follows.

[0205] A ruler is placed on the scanner bed so that it is oriented parallel to the side of the scanner glass. An image of the ruler (calibration image) is acquired in reflection mode with a resolution of 2400 dpi (approximately 94 pixels / mm) and 8-bit grayscale. The calibration image is saved as an uncompressed TIFF format file. After the calibration image is acquired, the ruler is removed from the scanner glass and all specimens are scanned under the same scanning conditions.

[0206] The measurement specimen is placed flat in the center of the scanner bed with the body-facing surface of the specimen facing the scanner glass surface. The corners and edges of the specimen are secured such that their original longitudinal and lateral dimensions are maintained as for the article before removal. The specimens are each oriented such that their long axis is aligned parallel to the side of the scanner glass surface and their short axis is aligned perpendicular. A black background is placed over the specimen, the scanner lid is closed, and a scan of the entire specimen is acquired with the same settings used for the calibration image. The specimen image is saved as an uncompressed TIFF format file. The remaining four replicate specimens are scanned and saved in a similar manner.

[0207] The specimen image is analyzed as follows: The calibration image file is opened in an image analysis program, and the image resolution is calibrated using an imaged ruler to determine the number of pixels per millimeter. The specimen image is then opened in the image analysis program, and the distance scale is set using the image resolution determined from the calibration image. Now, a longitudinal and lateral rectangular cross section (region of interest, or "ROI") is identified centered on the specimen, having a longitudinal dimension along the longitudinal axis of 60.0 mm and a lateral dimension of 30.0 mm, and the image of the holes present within the ROI is visually inspected. Now, using a software tool, a contour is manually drawn of each of the holes within the ROI (and any partial portions thereof at the edge of the ROI). The appropriate contour is drawn along the visually identifiable inner edge of the concentration of displaced fibers 503 around the hole. Escaped individual fibers that may escape the main structure and / or surrounding concentration of displaced fibers and cross into or through the main opening area of ​​the hole (as an illustrative example, stray individual fibers 504 shown in FIG. 5) are not considered to be subtracted from the hole area for purposes of this specification.) The software then measures the area within the outline (total and partial) of each individual hole within the ROI and rounds each to within 0.01 mm. 2 The areas of the individual holes are recorded in units of mm and their sum calculated. The area of ​​each individual hole is defined as the xy surface area within the visually identifiable outline of the open area, created by the mechanical penetration of the web and the xy displacement of the fibers in the drilling process that creates the holes through the web. (See, for example, FIG. 5, where the area 501 and visually identifiable boundary 502 of an individual hole are shown. The dark areas of the holes shown are an image of the black construction paper used as the specimen backing from which this particular image was made. The sum of the areas of all holes within the ROI is calculated to the nearest 0.01 mm. 2 Record the hole area in units. The hole area is then multiplied by the ROI area (1800 mm 2 ) and then multiply by 100 and record to the nearest 0.1% as the opening area.

[0208] Repeat the entire procedure for the remaining four replicate images. Calculate the arithmetic mean of the open area across all five replicates and report it to the nearest 0.1% as the average open area.

[0209] Acquisition Time and Rewet Measurement Method This method describes how to measure the gush acquisition time, interfacial free fluid amount, and low and high pressure rewet values ​​for absorbent articles loaded with new Artificial Menstrual Fluid (nAMF) prepared as described herein. Following a pretreatment step, a known amount of nAMF is introduced into the absorbent article three times. The time required for the absorbent article to acquire each dose of nAMF is measured using a see-through plate and an electronic interval timer. After each liquid dose, the interfacial free fluid (IFF) is measured gravimetrically as the fluid transfers from the bottom of the see-through plate to the filter paper. The low and high pressure rewet is then measured after the last liquid dose. The surface free fluid (SFF) is the amount of fluid remaining in the topsheet of the absorbent article. The SFF is measured by performing a rewet at low pressure (0.1 psi). Immediately after measuring the SFF, a higher pressure (0.5 psi) rewet is performed to determine the overall rewet of the absorbent article. All testing is performed indoors maintained at 23°C ± 2°C and 50% ± 2% relative humidity.

[0210] Equipment and Supplies Stain-proof plate configuration 6, 7, 8A and 8B, the see-through plate 601 is made from clear plexiglass or equivalent with overall dimensions of 10.2 cm length (y direction) x 10.2 cm width (x direction) x 3.1 cm height. (All positional and spatial references herein assume the orientation of the see-through plate as it would have if placed bottom-side down on a horizontal surface. All references to x, y and z directions in the description of this measurement method are only with reference to the x, y and z direction arrow indicators that appear in FIGS. 6, 7, 8A and 8B and do not necessarily apply to such references appearing elsewhere in this specification. A central test fluid well 608 with a circular opening and cylindrical walls 25 mm in diameter. defines a conical wall that opens at the top surface of the plate, extends vertically downward (z-direction) from the top surface of the plate to a depth of 15 mm, then bends radially inward, extending vertically downward another 7.5 mm from the top surface while uniformly tapering to a diameter matching that of the test fluid port 603. The test fluid port 603 is concentric / coaxial with the test fluid well 608, has a cylindrical wall with a diameter of 6.6 mm, and extends vertically downward another 5 mm from the top surface to the longitudinal fluid channel 607. A longitudinal fluid channel 607 is machined or otherwise formed in the bottom of the plate. The longitudinal fluid channel 607 has a depth from the bottom surface of the plate defined by vertical sidewalls that extend 3.5 mm upward (in the z-direction) at the midpoint of the channel (at the test fluid port 603) and then slope downward at an angle 607a of 0.72° toward each longitudinal end of the channel. The longitudinal fluid channel is open at the bottom surface of the plate to allow fluid to be introduced onto the underlying test specimen and to flow along the xy region bounded by the fluid channel 607. The fluid channel 607 is centered below the test fluid port 603 and its length extends in the y-direction perpendicular to the length of the x-direction path of the electrode 604 through the plate. The longitudinal fluid channel 607 has an x-direction width of 5 mm and a y-direction length of 80 mm, with rounded top corners with a radius 607b of 1.0 mm around the entire circumference of the channel.The walls at the opposing distal ends of the longitudinal fluid channel 607 have a cylindrical radius 609 of 2.5 mm in the xy plane.

[0211] Two rectangular cavities 602 (80.5 mm long (x-direction) x 24.5 mm wide (y-direction) x 25 mm deep (z-direction)) are positioned symmetrically outside of the fluid port 603 and are centered on the y-axis of the plate. These include an area of ​​10.2 cm x 10.2 cm = 104.04 cm for purposes of this specification, without subtracting the area defined by the longitudinal fluid channel 607. 2 0.10 psi (7.0 g / cm) over the total xy area defined by the plate. 2 ) of pressure. The electrodes 604 are embedded in the plate 601, each providing an electrical connection between one of two external banana jacks 606 and the other opposite location on the inner wall 605 of the longitudinal fluid channel 607. The bottom of the electrode 604, with its end exposed in the port 603, is 1.57 mm from the bottom surface of the plate 601. A circuit interval timer is connected to the jack 606 to monitor the impedance or resistance between the two electrodes 604 and measures the time from the introduction of nAMF into the port 603 (establishing an electrical connection between the electrodes and / or substantially decreasing the impedance or resistance between the electrodes) to the time the nAMF is expelled from the port 603 and the channel 607 into the test specimen to a level below the electrodes (breaking the electrical connection between the electrodes and / or substantially increasing the impedance or resistance between the electrodes). The circuit interval timer has a resolution of 0.01 seconds.

[0212] Pretreatment Plate A pretreatment plate (not shown) is used in combination with a pretreatment weight (not shown) to apply a droplet of nAMF to the surface of the test specimen to prime the specimen surface prior to the introduction of the full fluid dose specified below. The pretreatment plate is rectangular, made of clear plexiglass or equivalent, 14 inches (35.6 cm) long by 8 inches (20.3 cm) wide, with a thickness / caliper of approximately 0.25 inches (6.4 mm). The pretreatment plate is marked with five circular markers, each 5 mm in diameter, spaced 1 cm apart (center to center) and centrally located along the longitudinal axis of the plate. The five central markers are centered at the lateral midpoint of the longitudinal axis of the plate. These markers indicate the placement of the nAMF droplets. The markers are located on the underside of the pretreatment plate and can be milled or simply drawn with a permanent marker or equivalent in any manner that allows them to be seen through the top surface of the pretreatment plate.

[0213] Pretreatment weight The pretreatment weight (not shown) has x and y dimensions of 10.2 cm by 10.2 cm and is made of a flat, smooth, rigid material (e.g., stainless steel). The pretreatment weight has a total mass of 726 g + 0.5 g and extends from the bottom of the pretreatment weight to 104.04 cm. 2 0.10 psi (7.0 g / cm) over the surface area 2 ) pressure.

[0214] IFF rubber pad When measuring interfacial fluid volume, a flat surfaced rubber pad ("IFF rubber pad") (not shown) is used. The IFF rubber pad is made from high strength neoprene rubber (available from WWGrainger, Inc., part number 1DUV4, or equivalent) with a 40A durometer and 1 / 8 inch thickness / caliper, and cut to dimensions of 6 inches (15.2 cm) by 6 inches (15.2 cm).

[0215] Rewet Weight Assembly For the entire rewet portion of the test, 10.2 cm x 10.2 cm (104.04 cm 2) of surface area at 0.5 psi (35.1 g / cm 2 ) is required. The rewet weight assembly is constructed as follows.

[0216] A sheet of polyethylene film (approximately 25 microns thick, approximately 22.5 cm square in x-y directions, from any convenient source) is laid flat on a horizontal work surface. A piece of polyurethane foam (25 mm thick, 1.0 lb / ft density) is placed on the work surface. 3 A piece of clear plexiglass (10.2 cm x 10.2 cm, approximately 6.4 mm thick) is then stacked on top of the polyurethane foam. The polyethylene film is then gently pulled taut under the polyurethane foam, and the portion of the polyethylene film extending outward from under the polyurethane foam is wrapped around the polyurethane foam and the top of the plexiglass plate and secured around it with clear tape. A metal weight of suitable mass is selected and stacked on top of the plexiglass plate and secured to it such that the total mass of the assembly (rewet weight assembly) is 3.6 kg + 0.1 kg.

[0217] filter paper A varying number of filter paper layers (not shown) are required for the IFF, SFF and overall rewet steps. Prior to testing, the filter paper used should be conditioned for at least 2 hours at 23°C ± 2°C and 50% ± 2% relative humidity. A suitable filter paper has a basis weight of about 88 gsm, a thickness of about 249 microns, an absorption rate of about 5 seconds, and is available from Ahlstrom-Munksjo (Mt. Holly Springs, PA) as grade 632 or equivalent. Each sheet of filter paper is a square with dimensions of 5 inches by 5 inches (12.7 cm by 12.7 cm).

[0218] procedure 1) Prior to testing, the test sample (an example of the absorbent article of interest) is conditioned for at least 2 hours at 23°C ± 2°C and 50% ± 2% relative humidity. 2) Remove the test specimens from their outer packaging and, if necessary, open the packaging and unfold the product, taking care not to press down or pull on the product during handling. No attempt is made to smooth out wrinkles. Using scissors, cut any adhesive-coated release paper connecting the wings, if present, and place the specimen on a horizontal work surface with the surface facing the wearer facing up (i.e., outwardly facing side facing down). 3) For each sample, determine the dosing location as follows: The dosing location is the intersection of the midpoints of the longitudinal and transverse axes of the fluid management layer. Once the dosing location has been identified, use a black fine tip permanent marker to mark it with a small dot. 4) For each test of a sample, pretreat the test sample with nAMF as follows: a) Place the pre-treated plate on a horizontal work surface with the side with the circular markers facing down. b) Using a single channel fixed volume pipettor, dispense 50 μL of nAMF into each of the five positions above each of the five circular markers on the upper side of the pretreatment plate. c) Align the longitudinal axis of the test sample with the longitudinal axis of the pretreatment plate, place the test sample on the pretreatment plate such that the pre-marked dosing location on the test sample is centered on top of the central droplet of nAMF on the pretreatment plate, and place the test sample with the wearer-facing surface of the sample facing down, facing the pretreatment plate. d) After proper placement on top of the pretreatment plate, lower the test specimen into contact with the pretreatment plate, then quickly place the pretreatment weight over / onto the outwardly (upwardly) facing side of the test specimen so that it is centered over the top of the nAMF dosing location / center drop on the pretreatment plate, and immediately start a stopwatch-type timer set to sound an alarm after 40 seconds. After the 40 seconds have elapsed, remove the pretreatment weight from the test specimen and detach the test specimen from the pretreatment plate. Flip the test specimen so that the side facing the wearer is facing up, place it on a horizontal work surface, and proceed quickly to the next step. 5) The first acquisition time (ACQ-1) is measured as follows: a) Connect an electronic interval timer to the seepage plate 601 and set the timer to zero. b) Position the see-through plate 601 over the wearer-facing surface of the test sample, aligning the length (y-direction) axis of the underside longitudinal fluid channel 607 of the see-through plate 601 with the longitudinal axis of the test sample, ensuring that the fluid port 603 is centered above the pre-marked dosing location on the test sample. The central nAMF droplet applied to the test sample should now be visible through the fluid port 603 at the dosing location on the test sample. c) Once properly positioned on top of the test sample, the shine through plate 601 is gently placed on top / above the test sample. d) Using an adjustable volume pipettor, dispense 2.0 mL of nAMF into the fluid well 608 of the see-through plate 601. Distribute the fluid smoothly, without splashing, along the conical portion of the wall of the fluid well 608 within 3 seconds. When the fluid enters the port 603, an electrical connection between the electrodes 604 is established through the fluid and the circuit interval timer begins timing. When the fluid is captured by the test sample, the electrical connection between the electrodes 604 is broken and the circuit interval timer stops timing. Immediately after the circuit interval timer stops timing, start a stopwatch-type timer set to alarm after 2 minutes and leave the see-through plate on the test sample for this time. Immediately record the first capture time (ACQ-1) displayed on the circuit interval timer to the nearest 0.1 second. e) After 2 minutes, measure the First Interfacial Free Fluid (IFF-1) as follows: i) Place the IFF rubber pad on a horizontal work surface. Weigh the first new sheet of filter paper for this IFF-1 measurement (the IFF-1 filter paper sheet) and use the weight of the IFF-1 初期 The time is recorded as 0.05 seconds. Place the IFF-1 filter paper sheet on the IFF rubber pad, conform and center it on top of it. Quickly lift and move the strikethrough plate 601 from the test sample to the IFF-1 filter paper sheet so that the plate conforms and is centered on the filter paper, and immediately start a stopwatch timer set to sound an alarm after 8 minutes. ii) After 10 seconds have elapsed on the 8 minute timer, remove the strikethrough plate from the IFF-1 filter paper and gently place it back onto the test sample in the exact same position as before. iii) Within the next 10 seconds, measure the mass of the IFF-1 filter paper to the nearest 0.0001 g and 最終 Record as. 6) Measure the second acquisition time (ACQ-2) for the test sample as follows: a) After 8 minutes have elapsed according to the preset timer, use an adjustable volumetric pipettor to dispense a 4.0 mL dose of nAMF into the fluid well 608 of the see-through plate 601. Distribute the fluid smoothly, without splashing, along the conical portion of the wall of the fluid well 608 within 3 seconds. Immediately after the circuit interval timer stops timing, start a stopwatch-type timer set to alarm after 2 minutes, and leave the see-through plate on the test sample for this time. Immediately record the second capture time (ACQ-2) displayed on the circuit interval timer to the nearest 0.1 second. b) After 2 minutes, measure the second interfacial free fluid (IFF-2) as follows: i) Place the IFF rubber pad on a horizontal work surface. Weigh a second new sheet of filter paper for this IFF-2 measurement (the IFF-2 filter paper sheet) and compare the weight to the IFF-2 初期 The time is recorded as 100 seconds. Place the IFF-2 filter paper sheet on the IFF rubber pad, conform and center it on top of it. Quickly lift and move the strikethrough plate 601 from the test sample to the IFF-2 filter paper sheet so that the plate conforms and is centered on the filter paper, and immediately start a stopwatch timer set to sound an alarm after 8 minutes. ii) After 10 seconds have elapsed on the 8 minute timer, remove the strikethrough plate from the IFF-2 filter paper and gently place it back onto the test sample in the exact same position as before. iii) Within the next 10 seconds, measure the mass of the IFF-2 filter paper to the nearest 0.0001 g. 最終 Record as. 7) The third acquisition time (ACQ-3) is measured as follows: a) After 8 minutes have elapsed according to the preset timer, use an adjustable volumetric pipettor to dispense a 2.0 mL dose of nAMF into the fluid well 608 of the see-through plate 601. Distribute the fluid smoothly, without splashing, along the conical portion of the wall of the fluid well 608 within 3 seconds. Immediately after the circuit interval timer stops timing, start a stopwatch-type timer set to alarm after 2 minutes, and leave the see-through plate on the test sample for this time. Immediately record the third capture time (ACQ-3) displayed on the circuit interval timer to the nearest 0.1 second. b) After 2 minutes, measure the second interfacial free fluid (IFF-3) as follows: i) Place the IFF rubber pad on a horizontal work surface. Weigh the third new sheet of filter paper for this IFF-3 measurement (the IFF-3 filter paper sheet) and compare the weight to the IFF-3. 初期 The time is recorded as 100 seconds. Place the IFF-3 filter paper sheet on the IFF rubber pad, conform and center it on top of it. Quickly lift and move the strikethrough plate 601 from the test sample to the IFF-3 filter paper sheet so that the plate conforms and is centered on the filter paper, and immediately start a stopwatch timer set to sound an alarm after 8 minutes. ii) After 10 seconds have elapsed on the 8 minute timer, remove the see-through plate from the IFF-3 filter paper sheet and place it on its side so that the bottom of the plate is not touching the work surface. iii) Within the next 10 seconds, measure the mass of the IFF-3 filter paper sheet to the nearest 0.0001 g and 最終 Record as. 8) Measure the Surface Free Fluid (SFF) as follows: Weigh the first neat stack of 5 new sheets of filter paper for this SFF measurement (SFF filter paper stack) and equate the weight to the SFF 初期After the 8 minutes have elapsed according to the preset timer, the SFF filter paper stack is placed on top of the wearer-facing side of the test sample so that it is centered over the top of the dosing location. The see-through plate 601 is then placed on top of the SFF filter paper stack so that the bottom side of the plate is centered over the filter paper stack, and a stopwatch-type timer set to sound an alarm in 10 seconds is immediately started. After the 10 seconds have elapsed, the see-through plate 601 is removed from the filter paper stack and set aside. The mass of the SFF filter paper stack is measured to the nearest 0.0001 g, and the SFF 最終 Record this as . Proceed immediately to the next step. 9) Overall rewet is measured as follows: A second neat stack of 5 new sheets of filter paper for this REWET measurement (REWET filter paper stack) is weighed and the REWET 初期 The weight is recorded as the weight of the REWET paper stack. The REWET paper stack is placed on the wearer-facing side of the test specimen so that it is centered over the top of the dosing location. The rewet weight assembly is then placed on top of the REWET paper stack so that the weight is centered over the stack, and a stopwatch-type timer set to sound an alarm at 30 seconds is immediately started. After the 30 seconds have elapsed, the rewet weight assembly is removed and the mass of the REWET paper stack is measured to the nearest 0.0001 g, and then the REWET 最終 Record as. 10) Before testing the next sample, discard the test sample and thoroughly wash and then dry the seepage plate 601, including the fluid wells 608, fluid ports 603, longitudinal fluid channels 607, and bottom surface. 11) Perform the following calculations for each of the measured parameters as follows: IFF-1 最終 From IFF-1 初期 Calculate IFF-1 by subtracting IFF-2 from IFF-3 and record to the nearest 0.0001 g. 最終 From IFF-2 初期 Calculate IFF-2 by subtracting IFF-3 from IFF-4 and record to the nearest 0.0001 g. 最終 From IFF-3 初期Calculate IFF-3 by subtracting SFF from IFF-3 and record to the nearest 0.0001 g. 最終 From SFF 初期 Calculate the SFF by subtracting 0.0001g and record to the nearest 0.0001g. 最終 From REWET 初期 Calculate total rewet by subtracting and record to the nearest 0.0001 g. The entire procedure is repeated in the same manner for a total of three replicate test samples. The reported values ​​for each parameter are the average of three individually recorded measurements for each acquisition time (ACQ-1, ACQ-2, and ACQ-3) to the nearest 0.1 seconds, interfacial free fluid (IFF-1, IFF-2, and IFF-3) to the nearest 0.0001 grams, surface free fluid (SFF) to the nearest 0.0001 grams, and total rewet to the nearest 0.0001 grams.

[0219] Preparation of fresh artificial menstrual fluid (nAMF) Fresh artificial menstrual fluid (nAMF) is a mixture of defibrinated sheep blood, phosphate-buffered saline, and mucus components. nAMF is prepared to have a viscosity of 7.40-9.00 centipoise at 23 °C.

[0220] The viscosity of nAMF is measured using a low viscosity rotational viscometer (a suitable instrument is a Brookfield DV2T with a Brookfield UL adapter, or equivalent, available from AMETEK Brookfield, Middleboro, MA). The appropriate size spindle for the viscosity range is selected and the instrument is operated and calibrated according to the manufacturer. Measurements are taken at 23° C.±1° C. and 60 rpm. Results are reported to the nearest 0.01 centipoise.

[0221] Reagents required for nAMF preparation include defibrinated sheep blood having a hematocrit of 38% or greater (drawn under sterile conditions, available from Cleveland Scientific, Inc., Bath, Ohio, or a suitable equivalent source), gastric mucin (crude form, sterile, available from American Laboratories, Inc., Omaha, Neb., or a suitable equivalent source) having a target viscosity of 3-4 centistokes when prepared as a 2% aqueous solution, sodium phosphate dibasic anhydrous (reagent grade), sodium chloride (reagent grade), sodium phosphate monobasic monohydrate (reagent grade), sodium benzoate (reagent grade), benzyl alcohol (reagent grade), and distilled water (each available from VWR International or a suitable equivalent source).

[0222] Phosphate buffered saline consists of two individually prepared solutions (Solution A and Solution B). To prepare 1 L of solution A, add 1.38 ± 0.005 g of sodium phosphate monobasic monohydrate and 8.50 ± 0.005 g of sodium chloride to a 1000 mL volumetric flask and add distilled water to the volume of the vessel. Mix thoroughly. To prepare 1 L of solution B, add 1.42 ± 0.005 g of sodium phosphate dibasic anhydrous and 8.50 ± 0.005 g of sodium chloride to a 1000 mL volumetric flask and add distilled water to the volume of the vessel. Mix thoroughly. To prepare approximately 200 mL of phosphate buffered saline solution, add 49.50 g ± 0.10 g of solution A and 157.50 g + 0.10 g of solution B to a bottle of sufficient size with a tight-fitting lid. Then 1.0 g of sodium benzoate and 1.60 g of benzyl alcohol are added to the bottle along with a stir bar and set aside.

[0223] The mucus component of nAMF is a mixture of phosphate buffered saline and gastric mucin. The amount of gastric mucin added to the mucin component directly affects the final viscosity of the prepared nAMF. To determine the amount of gastric mucin required to obtain nAMF within the target viscosity range (7.4-9.0 centipoise at 23°C and 60 rpm), three batches of nAMF with various amounts of gastric mucin in the mucin component are prepared, then a least squares linear fit through the three points is performed and the exact amount required is interpolated from the concentration vs. viscosity curve. The appropriate range of gastric mucin is usually 13-15 grams per 400 mL batch of nAMF, but this can vary widely based on the source, age, and lot (production batch) of mucin.

[0224] To prepare approximately 200 mL of mucus component, a predetermined amount of gastric mucin is added to the bottle containing the previously prepared phosphate buffered solution and then capped. The bottle is placed on a wrist action shaker at maximum speed for 5 minutes. After 5 minutes, the flask with the mucus component is removed from the wrist action shaker and placed on a magnetic stir plate. Stir for at least 2 hours until no clumps of mucin are present, then remove the stir bar from the flask. The mucus component is mixed using a homogenizer at 10,000 rpm for 5 minutes. A suitable homogenizer is a T18 Ultra-Turrax with an S18N-19G dispersion tool (19 mm stator diameter, 12.7 mm rotor diameter, 0.4 mm gap between rotor and stator), both available from IKA Works, Inc. (Wilmington, NC) or a suitable equivalent source. After the final mixing step, measure and record the viscosity of the mucus component to the nearest 0.01 centipoise using a viscometer equipped with a UL adapter at 23 °C ± 1 °C and 20 rpm. Ensure that the viscosity of the prepared mucus component is within the target range of 9.0 - 11.0 centipoise.

[0225] nAMF is a 50:50 mixture of mucus component and sheep blood. Ensure that the temperature of the sheep blood and mucus component is 23°C ± 1°C. To prepare approximately 400 mL of nAMF, add 200 g of mucus component to a glass bottle of at least 500 mL capacity. Then, add 200 g of sheep blood to the bottle along with a stir bar. Mix on a magnetic stir plate until completely mixed. Ensure that the viscosity of the prepared nAMF is within the target range of 7.4 to 9.0 centipoise when measured at 23°C ± 1°C and 60 rpm using a viscometer with a UL adapter. If the viscosity is too high, the viscosity can be adjusted by adding 0.5 g of the previously prepared phosphate buffered saline solution in increments, followed by stirring for 2 minutes, and then rechecking the viscosity until it reaches the target range.

[0226] Certified nAMF must be refrigerated at 4°C unless intended for immediate use. After preparation, nAMF may be stored in an airtight container at 4°C for up to 48 hours. Prior to testing, nAMF must be kept at 23°C ± 1°C. After testing is completed, any unused portion is discarded. ***

[0227] Dimensions and values ​​disclosed herein should not be understood as being strictly limited to the exact numerical values ​​recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "approximately 40 mm."

[0228] All documents cited herein, including any cross-references or related patents or applications, are incorporated herein by reference in their entirety unless expressly excluded or otherwise limited. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest, or disclose any such invention, either alone or in combination with any other reference or references. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall govern.

[0229] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.

[0230] In view of the above description, the following non-limiting examples are contemplated, any of which, as well as others, may be claimed in one or more subsequent non-provisional patent applications based in whole or in part on the disclosure herein.

Claims

1. A feminine hygiene pad (10) having a longitudinal axis oriented along a y-direction, a transverse axis oriented along an x-direction and perpendicular to said longitudinal axis, and a pad caliper measured along a z-direction orthogonal to said longitudinal axis and said transverse axis, comprising a liquid pervious topsheet (20) comprising an integral fibrous nonwoven web, a fibrous fluid management layer (30) beneath said topsheet, an absorbent structure (40) beneath said fluid management layer, and a backsheet (50) beneath said absorbent structure. the fibrous nonwoven web comprises bicomponent staple topsheet fibers; the topsheet fibers have an average denier of 3.0 to 5.0; the topsheet fibers have a sheath-core bicomponent configuration, the sheath component comprises polyethylene (PE), the core component comprises polyethylene terephthalate (PET), and the weight ratio of PE:PET is 40:60 to 60:40; the topsheet fibers comprise a mixture of intermixed hydrophilic and hydrophobic fibers, the weight ratio of hydrophilic fibers to hydrophobic fibers being from 30:70 to 70:30, more preferably from 35:65 to 65:35, even more preferably from 40:60 to 60:40, and the hydrophilicity of the hydrophilic fibers is achieved by application of a surface treatment composition; The feminine hygiene pad (10), wherein the fibrous nonwoven web comprises a plurality of inter-fiber bonds randomly distributed within the fibrous nonwoven web along the x-direction, the y-direction, and the z-direction, the inter-fiber bonds being present where the sheaths of adjacent fibers are fusion bonded together without compression.

2. 2. The feminine hygiene pad of claim 1, wherein the fluid management layer (30) comprises carded staple fibers, including regenerated cellulose absorbent fibers at a weight fraction of 10 percent to 60 percent of the fluid management layer, bicomponent stiffening fibers at a weight fraction of 25 percent to 70 percent of the fluid management layer, and elastic fibers at a weight fraction of 15 percent to 70 percent of the fluid management layer.

3. The feminine hygiene pad of claim 2, wherein the stiffening fibers have a sheath-core configuration, the core component comprising PET and the sheath component comprising PE.

4. The feminine hygiene pad according to claim 2 or 3, wherein said elastic fibres are from 4 dtex to 15 dtex, or more preferably from 5 dtex to 12 dtex, or even more preferably from 6 dtex to 10 dtex.

5. 5. The feminine hygiene pad of claim 4, wherein the elastic fibers comprise a polymer selected from the group consisting of polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), and combinations thereof.

6. The feminine hygiene pad of any one of claims 1 to 5, wherein the fluid management layer comprises a plurality of randomly distributed interfiber bonds, wherein adjacent fibers are fusion bonded together without compression.

7. A feminine hygiene pad (10) having a longitudinal axis oriented along a y-direction, a transverse axis oriented along an x-direction and perpendicular to said longitudinal axis, and a pad caliper measured along a z-direction orthogonal to said longitudinal axis and said transverse axis, comprising a liquid pervious topsheet (20) comprising an integral fibrous nonwoven web, a fibrous fluid management layer (30) beneath said topsheet, an absorbent structure (40) beneath said fluid management layer, and a backsheet (50) beneath said absorbent structure. the fibrous nonwoven web comprises bicomponent staple topsheet fibers; the topsheet fibers have an average denier of 3.0 to 5.0; the topsheet fibers have a sheath-core bicomponent configuration, the sheath component comprises polyethylene (PE), the core component comprises polyethylene terephthalate (PET), and the weight ratio of PE:PET is 40:60 to 60:40; a major weight fraction, preferably all, of the fibrous nonwoven web is hydrophobic; The feminine hygiene pad (10), wherein the fibrous nonwoven web comprises a plurality of inter-fiber bonds randomly distributed within the fibrous nonwoven web along the x-direction, the y-direction, and the z-direction, the inter-fiber bonds being present where sheaths of adjacent fibers are fusion bonded together without compression.

8. 8. The feminine hygiene pad of claim 7, wherein the fluid management layer (30) comprises carded staple fibers, including regenerated cellulose absorbent fibers at a weight fraction of 10 percent to 60 percent of the fluid management layer, bicomponent stiffening fibers at a weight fraction of 25 percent to 70 percent of the fluid management layer, and elastic fibers at a weight fraction of 15 percent to 70 percent of the fluid management layer.

9. The feminine hygiene pad of claim 8, wherein the absorbent fibers are from 1 dtex to 7 dtex, or more preferably from 1.4 dtex to 6 dtex, or even more preferably from 1.7 dtex to 5 dtex.

10. The feminine hygiene pad according to claim 8, wherein said absorbent fibres are from 0.6 to 2.4 dtex, more preferably from 0.9 to 2.1 dtex, even more preferably from 1.1 to 1.9 dtex, most preferably from 1.3 to 1.7 dtex.

11. The feminine hygiene pad according to any one of claims 8 to 10, wherein said stiffening fibres are from 1.0 dtex to 6 dtex, more preferably from 1.5 dtex to 5 dtex, or even more preferably from 2.0 dtex to 4 dtex.

12. The feminine hygiene pad of any one of claims 8 to 11, wherein the stiffening fibers have a sheath-core configuration, the core component comprising PET and the sheath component comprising PE.

13. The feminine hygiene pad of any one of claims 8 to 12, wherein the fluid management layer comprises a plurality of randomly distributed interfiber bonds, wherein adjacent fibers are fusion bonded together without compression.

14. The feminine hygiene pad of any one of claims 1 to 13, wherein the integral fibrous nonwoven web of the topsheet comprises less than 10 weight percent, more preferably less than 5 weight percent, and even more preferably less than 1 weight percent of any combination of cotton fibers, other vegetable fibers, rayon fibers, or monocomponent fibers including polyester or polyamide.

15. The feminine hygiene pad of any one of claims 1 to 14, wherein the integral fibrous nonwoven web of the topsheet comprises less than 50 percent of its total wearer-facing surface area that is mechanically deformed along the z-direction, more preferably less than 35 percent, and even more preferably 25 percent or less.

Citation Information

Patent Citations

  • Loop member for a surface fastener and method for producing the same

    JP2016538046A

  • absorbent articles

    JP2020533155A

  • Absorbent article having improved comfort

    US20200315859A1